Assessing gross primary production dynamics in differently managed tallgrass prairies using Eddy covariance and satellite-derived estimates - Pradeep Wagle; Li Pan; Cheng Meng; Xiangming Xiao; Andres F. Cibils; Stacey A. Gunter (Science of The Total Environment, 2026)

UAV-satellite synergies for crop monitoring: current landscape, challenges, and future directions - Jiale Jiang; Qianyi Zhang; Kasper Johansen; Tao Cheng; Xia Yao; Qi Su; Matthew F. McCabe; Yan Zhu; Wenping Yuan (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Dust transport and impacts on secondary aerosol formation: Contrasting strong dust and floating dust events - Yanfen Lin; Qingyan Fu; Ziwei Liu; Zhijian Ding; Fan Yang; Ali Darvishi Boloorani; Cheng Huang; Juntao Huo; Qian Wang; Jia Chen; Qiongzhen Wang; Sabur F. Abdullaev; et al. (Atmospheric Environment, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Crimean speleothems reveal 50,000 years of climate variability and contrasting controls across the Black Sea region - Yidong Li; Christoph Spötl; Jonathan L. Baker; Sophie F. Warken; Sergey Tokarev; Gennady Amelichev; Hai Cheng; Aaron Mielke; Gabriella Koltai; Yuri Dublyansky (Quaternary Science Reviews, 2026)

Correction to “Choline chloride enables low-severity NaOH/Triton-X 100 pretreatment and lignin upgrading to enriched aromatic bio-oil and porous biochar” [Chem. Eng. J. 2026;538:176853. https://doi.org/10.1016/j.cej.2026.176853] - S. Al Azad; E. Kargaran; M. Saleknezhad; Y. Cheng; C. Quan; J. Chen; C. Sun; M. Madadi; F. Sun (Chemical Engineering Journal, 2026)

Habitat and Thermal Breadth Shape Climate‐Driven Range Shifts in Arctic Birds - Zhichang Cheng; Jente Ottenburghs; Willem F. de Boer (Journal of Biogeography, 2026)
Aim Rapid climate change is reshaping Arctic ecosystems and altering species' breeding distributions. We assessed climate‐driven breeding range shifts of Arctic birds and examined how functional traits, including morphology, habitat breadth, and thermal niche breadth, influence these shifts. Location European and North American Arctic. Taxon Arctic‐breeding bird species in the orders Anseriformes, Charadriiformes and Passeriformes. Method We quantified range shift metrics (i.e., record‐frequency‐weighted centroid latitude change and moving distance) between past (1960–1999) and current (2000–2024) periods using species occurrence data. Changes in suitable breeding distributions were estimated with species distribution models. The effects of functional traits on range shifts were evaluated using generalized linear models for each of the focal taxonomic groups, with continent‐level PGLS models across all species. Results Climatic trends differed markedly between the European and North American Arctic, resulting in region‐specific range shift responses. A significant interaction between habitat breadth and thermal niche emerged, as habitat breadth was positively associated with range shifts in species with narrow thermal breadth and lower critical minimum temperature, but negatively associated with shifts in species with broad thermal breadth and higher critical minimum temperature. Morphological traits linked to dispersal ability showed generally weak effects, and migratory strategy and trophic guild exhibited no consistent influence across taxa or regions. Although sensitivity analyses supported the main patterns, uneven sampling coverage, local record clustering, and unequal sample sizes limited our ability to fully disentangle biological range shifts from changes in sampling effort. Main Conclusions Trait interactions were more influential than single traits, indicating that species' responses to climate change depend on multidimensional trait combinations. Single functional traits provided limited explanatory power for Arctic bird range shifts and were strongly region and taxon‐dependent. Incorporating regional context and trait interactions is therefore essential for improving predictions of biodiversity responses to ongoing climate change.

Not the same plastics: Comparing abundance and composition of marine macro-litter in mangroves and beaches in Southeast Asia - Jenny Fong; Ashwini Suresh Kumar; Cheng Ling Lim; Muhammad Reza Cordova; Pham T. Hoa; Deo Florence L. Onda; Kim John N. Balboa; Norchel Corcia F. Gomez; Mochamad Riza Iskandar; Muhammad Taufik Kaisupy; Swietenia Puspa Lestari; Pham Ngoc; et al. (Journal of Environmental Management, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A T4SS effector directly disarms competing antibacterial T6SSs by hijacking their conserved spike component - Dan Xiong; Jinxing Liao; Zhiyuan Zhang; Julien F. Giraud; Xiuyuan Li; Dongjing Cheng; Bingxin Wang; Limin Wang; Xiaolong Shao; Long Lin; Jinshui Zheng; Xiangyang Li; et al. (Science China Life Sciences, 2026)

Heavy metals and per- and polyfluoroalkyl substances in breast milk: associations with infant birth outcomes in an E-waste recycling area - Yueyuan Fan; Hui Wang; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Cheng‑Sheng Zhu; Xian Liang Sun (Environmental Geochemistry and Health, 2026)

Predation, Climate and Species Traits Interact to Shape Global Patterns of Avian Nest Architecture - Stephanie Y. Chia; Yu Tsai‐Chen; Yi‐Ru Cheng; Mao‐Ning Tuanmu; William F. Fagan (Global Ecology and Biogeography, 2026)
Aim Bird nest structures are critical for reproductive success and vary widely across species. However, the ecological and evolutionary drivers behind enclosed nests (domes and cavities) remain unclear, with previous studies yielding conflicting results. Leveraging recently available comprehensive nest trait data, we aim to clarify whether enclosed nests primarily function as protection from predation or for regulation of microclimate. Location Global. Time Period Contemporary (environmental data from 1981 to 2010). Major Taxa Studied Birds (Aves). Methods Using phylogenetic logistic regression models for 7427 bird species, we examined whether the observed relationships between nest structure and potential environmental drivers and species traits were consistent with the predictions of the two functional hypotheses. To explore potential variations in the function, we built separate models for domes and cavities, as well as for passerines and non‐passerines. Results Predation risk increases the likelihood of dome use, especially in passerines, where a stronger increase is among the species that are more susceptible to nest predation such as ground‐nesting, non‐cooperative and larger clutch size species. Climatic effects are more pronounced in cavity nesters, with aridity promoting cavity use among passerines, and both cold and hot temperatures increasing cavity use among small non‐passerine species. Main Conclusions Different types of enclosed nests correspond to distinct environmental challenges, with dome nests primarily associated with predation pressure and cavities with adverse climatic conditions. These findings contribute to resolving long‐standing debates about the functional significance of enclosed nests and offer insights into the evolution of avian nest structures.

Optimal cost and multi-objective mixture design for low-carbon HPC considering carbon fees - Min-Yuan Cheng; Akhmad F. K. Khitam; Quoc-Tuan Vu; Hsi-Shiou Chao (Environment, Development and Sustainability, 2026)

The SPoRC Stock Assessment Package: A Generalized Next‐Generation Platform to Assess Spatial, Age and Sex‐Structured Populations - Matthew LH. Cheng; Daniel R. Goethel; Curry J. Cunningham; Peter‐John F. Hulson; James N. Ianelli; Kristen L. Omori (Fish and Fisheries, 2026)
Fisheries managers increasingly rely on stock assessment models to provide sustainable management advice, which must balance complex and competing objectives. Although assessment models necessitate simplifying assumptions, there is increasing recognition to improve the integration of realistic biological and fishery dynamics. While ongoing and future development of increasingly complex stock assessments requires increased capacity (i.e., time, training, and personnel), there are concerns that the growing demand for assessment advice cannot be adequately fulfilled under current resources. To address these needs, we present the Stochastic Population over Regional Components (SPoRC) model, a modern integrated analysis platform that is generalized, modular and developed in a user‐friendly programming language (R with Template Model Builder, RTMB). Development of SPoRC emphasized consideration of age, sex, and spatial dynamics at the outset, while ensuring the ability to integrate diverse data sources (e.g., catch, abundance indices, age/length compositions and tagging). Moreover, state‐space specification of time‐varying processes through random effects and robust simulation capabilities were primary design features. Here, we highlight SPoRC's utility in cohesively implementing single‐and multi‐region applications, its ability to estimate time‐varying processes as random effects, and the potential to conduct closed‐loop simulations for evaluating the robustness of management procedures. By developing a generalized assessment platform in a user‐friendly R package, we suggest that SPoRC reduces barriers to implementation of next‐generation stock assessment models and facilitates team‐based model development, which will ultimately help improve the capacity to implement stock assessments globally.

Recent advance in mycotoxin mitigation using food and agricultural by-products - Hailian Wei; Jin Mao; Qi Zhang; Ling Cheng; Xianglong Yang; Antonio F. Logrieco; Peiwu Li (Trends in Food Science & Technology, 2026)

Adaptive infrastructure intelligence: integrated urban stormwater management framework for climate-resilient cities - Mayao Cheng; Haytham F. Isleem; Ghanshyam G. Tejani; Ali Jahami (Journal of Hydrology, 2026)

Timescales for magma-storage and re-melting of mushes in the Gangdese active continental margin - Pengsheng Dong; Roberto F. Weinberg; Di-Cheng Zhu; Qing Wang; Li Liu; Liang-Liang Zhang; Jin-Cheng Xie; Oliver Nebel (Earth and Planetary Science Letters, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Deconjugation enzymes - pitfalls, contamination risks, and practical insights from human biomonitoring of bisphenols, phthalates, and oxidative stress markers - Ian Zammit; Yuya Cheng; Daniel Bury; Xianyu Wang; Jochen F. Mueller; Holger M. Koch (International Journal of Hygiene and Environmental Health, 2026)

Deciphering the geological significance of carbonate clumped-isotope-based temperature during the Permian-Triassic transition in South China - Biao Chang; Zhaoyu Zeng; Xiaofeng Cheng; Weihao Zhang; Zhen Xu; Tianhu Pu; Chaojin Lu; William F. Defliese; Rui Wang; Xu Dai; Haijun Song; Genming Luo (Geochimica et Cosmochimica Acta, 2026)

From digital decision-support to policy implementation: An operational framework for agri-environmental schemes - A.C. Wartenberg; C. Cheng; C. Marples; H. Dettmann; K. Hemminger; F. Ghafarian; L. Schaan; M. Scoville; S.D. Bellingrath-Kimura (Biological Conservation, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Correction to: An automated pipeline to generate initial estimates for population Pharmacokinetic base models - Zhonghui Huang; Matthew Fidler; Minshi Lan; Iek Leng Cheng; Frank Kloprogge; Joseph F Standing (Journal of Pharmacokinetics and Pharmacodynamics, 2026)

Accurately tracking radial location dynamics of freeze-thaw front in tree stems under field conditions: a comprehensive model considering non-uniformity of stem water content distribution and electric-field attenuation of electromagnetic sensor - Yuxin Liu; Xiaofei Yan; Taisheng Du; Ricardo F. de Oliveira; Keyi Zhang; Qiang Cheng (Agricultural and Forest Meteorology, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Species-specific responses of fish sperm to thermal incubation and activation during short-term storage - Songpei Zhang; Shuang Peng; Yu Gao; Zhijun Ma; Thales S. França; Yu Cheng; Nururshopa Eskander Shazada; Fátima Fernández-García; Jaime Pérez-Sánchez; Juan F. Asturiano; Serhii Boryshpolets; Marek Rodina; et al. (Aquaculture, 2026)

Speleothem-based reconstruction of Holocene changes in monsoonal patterns and environmental conditions in Central Brazil - Marcela Eduarda Della Libera; Julio Cauhy; Cintia Stumpf; Roberto V. Santos; Francisco W. Cruz; Nicolas M. Stríkis; Luciana F. Prado; Jean-Sebastian Moquet; Michael Weber; Rebecca Orrison; Hai Cheng; R. Lawrence Edwards; et al. (Global and Planetary Change, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Hydrothermal extraction and characterization of hemicellulose from biomass as a natural emulsifier - Yilin Li; Shuo Jiang; Zhiyuan Xu; Yixiang Xu; Seunghee Yoon; Xuanbo Liu; Yifan Cheng; Sean F. O'Keefe; Jactone Ogejo; Feng Lin; Yiming Feng; Haibo Huang (Food Chemistry, 2026)

A new Myxospora ( Hypocreales, Sordariomycetes ) species from the Tibetan Plateau, China - Shu-Cheng He; Vinodhini Thiyagaraja; Chitrabhanu S. Bhunjun; Ruvishika S. Jayawardena; Putarak Chomnunti; F. Al-Otibi; Yun-Wei Zhao; Qi Zhao; Kevin D. Hyde (New Zealand Journal of Botany, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Techno-economic analysis of cost-competitive hard carbon production from biomass for sodium-ion batteries - Yilin Li; Yixiang Xu; Yifan Cheng; Sean F. O’Keefe; Jactone Ogejo; Feng Lin; Haibo Huang (Bioresource Technology, 2025)

An automated pipeline to generate initial estimates for population Pharmacokinetic base models - Zhonghui Huang; Matthew Fidler; Minshi Lan; Iek Leng Cheng; Frank Kloprogge; Joseph F Standing (Journal of Pharmacokinetics and Pharmacodynamics, 2025)
Nonlinear mixed-effects models rely on adequate initial parameter estimates for efficient parameter optimization. Poor initial estimates can result in failed model convergence or termination with incorrect parameter estimates. Non-compartmental analysis (NCA) and other manual methods have typically been used to derive initial estimates for pharmacokinetic (PK) parameters. However, NCA struggles with sparse data and recent advances in automated modeling increasingly emphasize the need for initial estimates that require no user input. This study aimed to develop an integrated pipeline for the computation of initial estimates applicable to various data types and model structures. The designed pipeline incorporated a custom-designed algorithm that leveraged data-driven methods to generate initial estimates for both structural and statistical parameters in population pharmacokinetic (PopPK) base models. The pipeline’s performance was evaluated across twenty-one simulated datasets and thirteen real-life datasets. The results suggested that this pipeline performed well in all test cases. Initial estimates recommended by the pipeline resulted in final parameter estimates closely aligned with pre-set true values in simulated datasets or with literature references in the case of real-life data. This study provides an efficient and reliable tool for delivering PK initial estimates for population pharmacokinetic modeling in both rich and sparse data scenarios. An open-source R package has been created.

Mixed Outcomes in Recombination Rates After Domestication: Revisiting Theory and Data - Madeline Bursell; Manav Rohilla; Lucia Ramirez; Yuhuan Cheng; Enrique J. Schwarzkopf; Rafael F. Guerrero; Caiti Smukowski Heil (Molecular Ecology, 2025)
The process of domestication has altered many phenotypes. Selection on these phenotypes has long been hypothesised to indirectly select for increases in the genome‐wide recombination rate. This hypothesis is potentially consistent with theory on the evolution of the recombination rate, but empirical support has been unclear. We review relevant theory, lab‐based experiments, and data comparing recombination rates in wild progenitors and their domesticated counterparts. We utilise population sequencing data and a deep learning method to infer genome‐wide recombination rates for new comparisons of chicken/red junglefowl, sheep/mouflon, and goat/bezoar. We find evidence of increased recombination in domesticated goats compared to bezoars but more mixed results in chicken and generally decreased recombination in domesticated sheep compared to mouflon. Our results add to a growing body of literature in plants and animals that finds no consistent evidence of an increase in genome‐wide recombination with domestication.

Hydrological variability in the Black Sea region during the last 670,000 years recorded in multi-proxy speleothem records from northern Türkiye - F. Held; H. Cheng; R.L. Edwards; T. Kipfer; O. Tüysüz; K. Koç; S. Affolter; D. Fleitmann (Quaternary Science Reviews, 2025)

From the hive to the brain: synergistic potential of honeybee products with alzheimer’s drugs - Hesham R. El-Seedi; Suzy Salama; Aya A. Shetaia; Mohamed H. Elashal; Aida Abd El-Wahed; Sercan Karav; Aamer Saeed; Mohammad A. Alzahrani; Xiaobo Zou; Lucian Hritcu; Guiguang Cheng; Mohamed F. Salem; et al. (Metabolic Brain Disease, 2025)

Avocado consumption patterns in the United States: National Health and Nutrition Examination Survey 2017-March 2020 and August 2021-August 2023 - F. Cheng; S. Morton; M. McCrory; A. Moshfegh; N. Ford (Journal of the Academy of Nutrition and Dietetics, 2025)

Chemical alteration of UO2 micro-particles in model lung systems - You Cheng Khng; Gianni F. Vettese; Satoshi Utsunomiya; Joyce W.L. Ang; Jessica M. Walker; Julia Parker; Thomas Neill; Katherine Morris; Liam Abrahamsen–Mills; Mirkka Sarparanta; Gareth T.W. Law (Journal of Hazardous Materials, 2025)

Ultrasonication degradation of per- and polyfluoroalkyl substances (PFAS) in synthetic environmental samples: Impact of ionic composition and water chemistry - Olalekan Simon Awoyemi; Chiedza F. Munyeza; Abhishek Sharma; Ravi Naidu; Cheng Fang (Journal of Water Process Engineering, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

Multi-objective optimization of anhydrous phosphogypsum-based composite cementitious materials - Y. Zhao; X. Zhou; Q. Zhou; H. Zhu; F. Cheng; H. Chen (International Journal of Environmental Science and Technology, 2025)

A review on the potential use of eubiotics in non-chicken poultry species - Caven M. Mnisi; Felix M. Njeri; Anderson N. Maina; Paul K. Waliaula; Veronica Cheng; Indibabale Kumalo; Chidozie F. Egbu; Elijah G. Kiarie (Tropical Animal Health and Production, 2025)
As the demand for poultry products increases, safe nutritional measures should be implemented to ensure successful diversification of the poultry industry with non-chicken poultry (NCP) species such as quail, turkey, ostrich, waterfowls, and guinea fowls. Thus, this review focuses on the current and future utility of eubiotics in NCP species by outlining the challenges and potential benefits that are associated with their utilization. Eubiotics are a group of feed additives, including probiotics, prebiotics, synbiotics, organic acids, and essential oils, that are safe and exhibit antimicrobial and immunomodulatory activities, prudent in an era where multi-drug antimicrobial resistance poses a grave threat to human health. Using eubiotics, separately or in combination, in NCP diets could enhance gut health, immune responses, growth performance, and product quality. However, their mechanisms of action are not fully understood, and their synergistic effects are not clearly outlined especially for NCP species. Moreover, inconsistent results have been reported, possibly due to various sources, application methods, production systems, bird types, and variations in rearing sites (macro- and micro-climatic conditions). We postulate that their extensive adoption in diets of NCP species could, in the future, deliver safe, efficient, and sustainable poultry production systems. We conclude that correct application methods, optimal dosages, and understanding of their synergistic actions could ensure alternative poultry systems that would contribute significantly to global food safety and nutrition security.

Misspecifying Sex‐Structured Dynamics in Stock Assessment Models - Matthew L. H. Cheng; Daniel R. Goethel; Peter‐John F. Hulson; Michael J. Wilberg; Craig Marsh; Curry J. Cunningham (Fish and Fisheries, 2025)
Sex‐specific variation in population demography and life‐history traits (e.g., growth, natural mortality) is common in many fish populations. Differences in these processes by sex can dictate population dynamics and influence how harvesters interact with the resource. Across various fisheries management systems, stock assessment models (SAMs), which mathematically represent population age and/or size structure, are widely utilised to estimate fish population status and provide sustainable harvest recommendations. However, few studies have examined the implications of alternative modelling assumptions when incorporating sex‐specific dynamics in SAMs. For instance, the impacts of simultaneously ignoring sex‐specific variations in growth, selectivity, and natural mortality on SAM performance have not been explored. In this study, a simulation‐estimation framework was developed for a sexually dimorphic fish population to: (1) assess the consequences of ignoring sexual dimorphism (i.e., growth, natural mortality, and selectivity) and the benefits of using sex‐specific catch data to inform the estimation of these processes, (2) evaluate the implications of incorrect modelling assumptions regarding sex ratio at birth, and (3) develop advice for parameterising observation likelihoods to describe sex‐specific composition data. Correctly parameterising sex‐specific variation in life‐history traits led to more robust population estimates and catch advice. Conversely, SAMs ignoring these variations yielded biased estimates of biomass and harvest recommendations. Collectively, our results underscore that oversimplified assumptions about sex‐specific variations in SAMs can lead to poor management advice. Moreover, results emphasise the need for routine collection of sex‐specific data to support the development of biologically realistic models.

Development of an interdigitated electrode sensor for monitoring tobacco leaf relative water content in bulk curing barn - Xianglin Cheng; Weimin Guo; Yanling Zhang; Xiaofei Yan; Junhui Li; Ricardo F. de Oliveira; Qiang Cheng; Qiang Xu (Computers and Electronics in Agriculture, 2025)

Selective production of olefins from methanol over a heteroatomic SAPO-34 zeolite - Zhaodong Zhu; Mengtian Fan; Meng He; Bing An; Yinlin Chen; Shaojun Xu; Tianze Zhou; Alena M. Sheveleva; Meredydd Kippax-Jones; Lutong Shan; Yongqiang Cheng; Hamish Cavaye; et al. (Science Bulletin, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Low-cost composite electrodes by active Fe3O4 (111) of fly ash magnetic-sphere for efficient electrochemical overall water splitting - T. Cheng; C. Chen; M. Wen; F. Pan; X. Zhang; H. Ma; B. Hou; X. Xin (International Journal of Environmental Science and Technology, 2025)

Correction: Associations Between Heavy Metal Exposure from Milk and Steroid Hormones in Mothers - Zheng Wang; Caixia Liang; Li Li Shi; Cheng-Sheng Zhu; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Xian Liang Sun; Jiancong Shan (Biological Trace Element Research, 2025)

Negative emotional eating patterns in Chinese adolescents: A replication and longitudinal extension with latent profile and transition analyses - Hongbin Weng; Wesley R. Barnhart; Hana F. Zickgraf; Urvashi Dixit; Yawei Cheng; Gui Chen; Jinbo He (Appetite, 2025)

A mathematical proof comparing the statistical properties between two common approaches for parameterizing sex-composition likelihoods in fishery stock assessments - Matthew LH. Cheng; Peter-John F. Hulson; Daniel R. Goethel; Curry J. Cunningham (Fisheries Research, 2025)

Evolution of continental inputs and watermass during cretaceous oceanic anoxic event 2 in the Neo-Tethyan region: Evidence from Nd-isotopes in southern Tibet - Xiaofeng Cheng; Biao Chang; Zhaoyu Zeng; Lian Zhou; Junhua Huang; William F. Defliese; Shucheng Xie (Chemical Geology, 2025)

Associations Between Heavy Metal Exposure from Milk and Steroid Hormones in Mothers - Zheng Wang; Caixia Liang; Li Li Shi; Cheng-Sheng Zhu; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Xian Liang Sun; Jiancong Shan (Biological Trace Element Research, 2024)

New dielectric-based smart sensor with multi-probe arrays for in-vivo monitoring of trunk water content distribution of a tree in a poplar stand - Xianglin Cheng; Xiaotong Wu; Yufan Zhu; Yang Zhao; Benye Xi; Xiaofei Yan; Ricardo F. de Oliveirad; Qiang Cheng (Computers and Electronics in Agriculture, 2024)

Anorthosites produced by water-fluxed anatexis of deep arc gabbros, Gangdese batholith, Tibet - Pengsheng Dong; Roberto F. Weinberg; Di-Cheng Zhu; Eleanor C.R. Green; Jiankang Yi; Peter A. Cawood; Shi-Min Li; Shaorong Chen (Earth and Planetary Science Letters, 2024)

North Atlantic Heat Transport Convergence Derived from a Regional Energy Budget Using Different Ocean Heat Content Estimates - B. Meyssignac; S. Fourest; Michael Mayer; G. C. Johnson; F. M. Calafat; M. Ablain; T. Boyer; L. Cheng; D. Desbruyères; G. Forget; D. Giglio; M. Kuusela; et al. (Surveys in Geophysics, 2024)
This study uses an oceanic energy budget to estimate the ocean heat transport convergence in the North Atlantic during 2005–2018. The horizontal convergence of the ocean heat transport is estimated using ocean heat content tendency primarily derived from satellite altimetry combined with space gravimetry. The net surface energy fluxes are inferred from mass-corrected divergence of atmospheric energy transport and tendency of the ECMWF ERA5 reanalysis combined with top-of-the-atmosphere radiative fluxes from the clouds and the Earth’s radiant energy system project. The indirectly estimated horizontal convergence of the ocean heat transport is integrated between the rapid climate change-meridional overturning circulation and heatflux array (RAPID) section at 26.5°N (operating since 2004) and the overturning in the subpolar north atlantic program (OSNAP) section, situated at 53°–60°N (operating since 2014). This is to validate the ocean heat transport convergence estimate against an independent estimate derived from RAPID and OSNAP in-situ measurements. The mean ocean energy budget of the North Atlantic is closed to within ± 0.25 PW between RAPID and OSNAP sections. The mean oceanic heat transport convergence between these sections is 0.58 ± 0.25 PW, which agrees well with observed section transports. Interannual variability of the inferred oceanic heat transport convergence is also in reasonable agreement with the interannual variability observed at RAPID and OSNAP, with a correlation of 0.54 between annual time series. The correlation increases to 0.67 for biannual time series. Other estimates of the ocean energy budget based on ocean heat content tendency derived from various methods give similar results. Despite a large spread, the correlation is always significant meaning the results are robust against the method to estimate the ocean heat content tendency.

Concurrent measurements of bark and xylem water contents in Malus pumila Mill. stems using improved flexible sensors - Xianglin Cheng; Xiaofei Yan; Zhongyi Wang; Junhui Li; Ricardo F. de Oliveira; Taisheng Du; Qiang Cheng (Agricultural and Forest Meteorology, 2024)

Pre-treatments to reduce metabolism in adult green-lipped mussel, Perna canaliculus, in preparation for live transportation - M. C. F. Cheng; L. N. Zamora; N. L. C. Ragg; A. J. R. Hickey; B. J. Dunphy (Aquaculture International, 2024)
Improved sustainability of aquaculture can be achieved by reducing product wastage post-harvest. Aquaculture of the green-lipped mussel, Perna canaliculus , is an important industry for New Zealand, which increasingly exports to live markets. Live transport can keep mussels fresh, but mussels could also be susceptible to handling stresses. To remedy this, pre-treatments that make mussels metabolically depressed, and thus potentially less sensitive to external stressors, were explored. As indicators of depressed metabolism, heart rate (HR), inferred cardiac output (PCO), and relative gaping magnitude (RGM) were simultaneously monitored in mussels experiencing different temperatures, dissolved oxygen levels and anaesthetic (MgCl 2 ) concentrations to compare their efficacy in inducing suppressed metabolism of adult P. canaliculus . We found complex interactions between HR, PCO, and RGM in response to these conditions; however, overall, these response variables were significantly correlated. Mussels showed depressed HR and PCO by up to 100% at 4 °C within 2 h, with correspondingly decreased RGM of up to 48%. Similarly, mussels immersed in 40 g L −1 MgCl 2 suppressed HR by up to 97%, accompanied by up to 76% decrease in PCO, and a slight increase in RGM (11%) after 2 h. While responses were variable, low DO levels suppressed HR by up to 50%, yet PCO and RGM increased two- and threefold relative to control groups. The results of the present study indicated that 4 °C and 40 g MgCl 2 L −1 were more effective conditions as pre-treatments than low dissolved oxygen lower the metabolism of P. canaliculus before live transport.

Comparing evaporation from water balance framework and multiple models on a global scale - Jinghua Xiong; Abhishek; Chong Zhang; Li Xu; Hrishikesh A. Chandanpurkar; James S. Famiglietti; Pat J.-F. Yeh; Zhongbo Yu; Ningpeng Dong; Haoran Hao; Shuang Yi; Lei Cheng; et al. (Journal of Hydrology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A Prospective Cohort Study of the Impact of Maternal Avocado Consumption During Pregnancy on Offspring Allergic Diseases: The Kuopio Birth Cohort Study (KuBiCo) - F. Cheng; S. Hantunen; L. Keski-Nisula; K. Backman; N. Ford (Journal of the Academy of Nutrition and Dietetics, 2024)

Photoelectron‐promoted metabolism of sulphate‐reducing microorganisms in substrate‐depleted environments - Chao Zhong; Anhuai Lu; Hailiang Dong; Shan Huang; Liang Shi; Yanan Shen; Yangjian Cheng; Yiran Dong; Xiangzhen Li; Jie Xu; Jinren Ni; Michael F. Hochella; et al. (Environmental Microbiology, 2024)
Sulphate‐reducing microorganisms, or SRMs, are crucial to organic decomposition, the sulphur cycle, and the formation of pyrite. Despite their low energy‐yielding metabolism and intense competition with other microorganisms, their ability to thrive in natural habitats often lacking sufficient substrates remains an enigma. This study delves into how Desulfovibrio desulfuricans G20, a representative SRM, utilizes photoelectrons from extracellular sphalerite (ZnS), a semiconducting mineral that often coexists with SRMs, for its metabolism and energy production. Batch experiments with sphalerite reveal that the initial rate and extent of sulphate reduction by G20 increased by 3.6 and 3.2 times respectively under light conditions compared to darkness, when lactate was not added. Analyses of microbial photoelectrochemical, transcriptomic, and metabolomic data suggest that in the absence of lactate, G20 extracts photoelectrons from extracellular sphalerite through cytochromes, nanowires, and electron shuttles. Genes encoding movement and biofilm formation are upregulated, suggesting that G20 might sense redox potential gradients and migrate towards sphalerite to acquire photoelectrons. This process enhances the intracellular electron transfer activity, sulphur metabolism, and ATP production of G20, which becomes dominant under conditions of carbon starvation and extends cell viability in such environments. This mechanism could be a vital strategy for SRMs to survive in energy‐limited environments and contribute to sulphur cycling.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Co-contamination and interactions of multiple mycotoxins and heavy metals in rice, maize, soybeans, and wheat flour marketed in Shanghai City - Zuoyin Zhu; Wenbo Guo; Haisheng Cheng; Hanke Zhao; Jie Wang; Mohamed F. Abdallah; Xinli Zhou; Hulong Lei; Weilong Tu; Hongyang Wang; Junhua Yang (Journal of Hazardous Materials, 2024)

A Panel of miRNA Biomarkers Common to Serum and Brain-Derived Extracellular Vesicles Identified in Mouse Model of Amyotrophic Lateral Sclerosis - Natasha Vassileff; Jereme G. Spiers; John D. Lee; Trent M. Woodruff; Esmaeil Ebrahimie; Manijeh Mohammadi Dehcheshmeh; Andrew F. Hill; Lesley Cheng (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is a progressive motor neuron disease characterised by the deposition of aggregated proteins including TAR DNA-binding protein 43 (TDP-43) in vulnerable motor neurons and the brain. Extracellular vesicles (EVs) facilitate the spread of neurodegenerative diseases and can be easily accessed in the bloodstream. This study aimed to identify a panel of EV miRNAs that can capture the pathology occurring in the brain and peripheral circulation. EVs were isolated from the cortex (BDEVs) and serum (serum EVs) of 3 month-old and 6-month-old TDP-43*Q331K and TDP-43*WT mice. Following characterisation and miRNA isolation, the EVs underwent next-generation sequencing where 24 differentially packaged miRNAs were identified in the TDP-43*Q331K BDEVs and 7 in the TDP-43*Q331K serum EVs. Several miRNAs, including miR-183-5p, were linked to ALS. Additionally, miR-122-5p and miR-486b-5p were identified in both panels, demonstrating the ability of the serum EVs to capture the dysregulation occurring in the brain. This is the first study to identify miRNAs common to both the serum EVs and BDEVs in a mouse model of ALS.

Extreme climate events and future population exposure under climate change in the Huaihe River basin of China based on CMIP6 multimodel ensembles projections - Tian Yao; Chuanhao Wu; Pat J.‐F. Yeh; Jiayun Li; Xuan Wang; Jiahao Cheng; Jun Zhou; Bill X. Hu (International Journal of Climatology, 2024)
The Huaihe River basin (HRB) of China located in the climate transition zone between warm temperate and subtropical areas is highly sensitive to climatic change. However, the changes in future climate extreme events under anthropogenic warming and the population exposure to these climate extremes in HRB remain unexplored. Here, using the eight commonly used extreme climate indices and based on the bias‐corrections of 16 global climate models (GCMs) in CMIP6, we present a projection and uncertainty analysis of extreme events and investigate the corresponding population exposure risk in HRB under three shared socioeconomic pathways (SSP1‐2.6, SSP2‐4.5, SSP5‐8.5). The 16‐GCM ensemble mean projects an evident warming trend under all three scenarios with a total increase of 25.6–68.0 days in summer days (>25°C) by the end of the century in HRB. Larger increases (decreases) in maximum and minimum temperatures (frost days) are projected in the western HRB. Very heavy rain days (R20mm), maximum 5‐day precipitation (RX5day) and simple daily intensity index (SDII) will experience intensification across most of HRB (especially in southern and western HRB). The consecutive dry days is projected to decrease in northwestern HRB and increase in southern HRB. However, there is a large spatial variability in GCM uncertainty with a higher SSP scenario generally having higher uncertainty. Increases in summer days and R20mm exacerbate population exposure in HRB in near future (2030–2059), but in far future (2070–2099) although summer days (R20mm) continues to rise, population exposure is expected to decrease due to the rapid decline in population density.

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Capturing uncertainty when modelling environmental drivers of fish populations, with an illustrative application to Pacific Cod in the eastern Bering Sea - André E. Punt; Michael G. Dalton; Grant D. Adams; Steven J. Barbeaux; Wei Cheng; Albert J. Hermann; Kirstin K. Holsman; Peter-John F. Hulson; Thomas P. Hurst; Alberto Rovellini (Fisheries Research, 2024)

Blueprint for the design, construction, and validation of a plastic and phthalate-minimised laboratory - Cassandra Rauert; Xianyu Wang; Nathan Charlton; Chun-Yin Lin; Cheng Tang; Ian Zammit; Ayomi Jayarathne; Christos Symeonides; Emily White; Michael Christensen; Valentina Ponomariova; Jochen F. Mueller; et al. (Journal of Hazardous Materials, 2024)

PARSIFAL: A toolkit for triple-GEM parametrized simulation - A. Amoroso; R. Baldini Ferroli; I. Balossino; M. Bertani; D. Bettoni; F. Bianchi; A. Bortone; A. Calcaterra; S. Cerioni; W. Cheng; G. Cibinetto; A. Cotta Ramusino; et al. (Computer Physics Communications, 2024)

Spring phytoplankton bloom phenology during recent climate warming on the Bering Sea shelf - Jens M. Nielsen; Michael F. Sigler; Lisa B. Eisner; Jordan T. Watson; Lauren A. Rogers; Shaun W. Bell; Noel Pelland; Calvin W. Mordy; Wei Cheng; Kirill Kivva; Sage Osborne; Phyllis Stabeno (Progress in Oceanography, 2024)

Advisory Editor profile: Qiqun Cheng - Margaret F. Docker; Qiqun Cheng (Environmental Biology of Fishes, 2023)

Evaluation and identification of chemical migrants leached from baby food pouch packaging - Cheng Tang; María José Gómez Ramos; Amy Heffernan; Sarit Kaserzon; Cassandra Rauert; Chun-Yin Lin; Jochen F. Mueller; Xianyu Wang (Chemosphere, 2023)

UHP metamorphism, decompression anatexis and retrogression of garnet-bearing metagranite and granitic gneiss from the Dabie orogen during continental collision - Cheng-Wei Zhang; Yang Yang; Yi-Can Liu; C. Groppo; F. Rolfo (Lithos, 2023)

Castration reduces mortality and increases resilience in male mice: what is next? - Nisi Jiang; Catherine J. Cheng; Randy Strong; James F. Nelson (GeroScience, 2023)

Insights on Feeding Practices from a National Survey of Daycare Caregivers & an Intervention to Increase Feeding of Avocados to Infants & Toddlers - F. Cheng; N. Ford; S. Maniscalco; T. Psota (Journal of the Academy of Nutrition and Dietetics, 2023)

Spatiotemporal characteristics of ozone and the formation sensitivity over the Fenwei Plain - H.H. Ren; Y. Cheng; F. Wu; Z.L. Gu; J.J. Cao; Y. Huang; Y.G. Xue; L. Cui; Y.W. Zhang; J.C. Chow; J.G. Watson; R.J. Zhang; et al. (Science of The Total Environment, 2023)

Comparative Analysis of Rhizosphere and Endophytic Microbial Communities Between Root Rot and Healthy Root of Psammosilene tunicoides - Wen. T. Yang; Guo. D. Li; Jun. N. Li; Cheng. F. Yang; Xiao. M. Zhang; Ai. L. Zhang (Current Microbiology, 2023)
The wild resources of Psammosilene tunicoides have decreased sharply because of the long-term mining and excavation, which has led to the increased demand for its artificial cultivation. However, root rot represents a significant obstacle leading to a poor quality and product of P. tunicoides . Previous reports have not focused on root rot in P. tunicoides. Therefore, this study explores the rhizospheric and root endophytic microbial community structure and composition of healthy and root rot P. tunicoides to understand the mechanism underlying root rot . The properties of the rhizosphere soil were assessed using physiochemical methods, and the bacterial and fungal populations were studied through amplicon sequencing of the 16S rRNA genes and ITS regions in the root and soil. Compared to healthy samples, the pH, hydrolysis N, available P, and available K were significantly decreased in the diseased samples while the organic matter and total organic carbon were significantly increased in the diseased samples. Redundancy analysis (RDA) showed that soil environmental factors are related to changes in the root and rhizosphere soil microbial community of P. tunicoides indicating that the physiochemical properties of soil affect plant health. Alpha diversity analysis showed that the microbial communities of healthy and diseased samples were similar. Some bacterial and fungal genera were significantly increased or decreased ( P < 0.05) in diseased P. tunicoides , and certain microbial factors that antagonized root rot were further explored. This study provides an abundant microbial resource for future studies and contributes to improving soil quality and P. tunicoides agricultural production.

A Location-Allocation Model with Obstacle and Capacity Constraints for the Layout Optimization of a Subsea Transmission Network with Line-Shaped Conduction Structures - Cheng Hong; Yuxi Wang; Segen F. Estefen (Journal of Marine Science and Engineering, 2023)
The idea of this paper comes from the need for a practical layout design for the subsea pipe line network and the power transmission network of offshore wind farms with subsea cables, which are both subsea transmission networks with line-shaped conduction structures. In this paper, this practical need is treated as an location-allocation problem, with the objective of minimizing the total cost, and a mixed-integer linear programming model (MILP) for layout optimization is developed. Through the model, the locations of service centers and theit corresponding sizes, the allocations between customers and service centers, as well as the transmission routes can all be figured out. This work makes two key contributions. First, facilities’ capacity restrictions and the avoidance of subsea obstacles are both integrated, making the description of the layout closer to practical situations. Secondly, a “global to local” search process based on the Delaunay triangulation method is constructed to solve the model, resulting in a high-quality solution. An offshore field layout design scenario is taken as a case study, through which the validity, feasibility, and stability of the proposed model, as well as the solution strategy, are presented. Furthermore, in the case study, the effect of the manifold number on the layout optimization is analyzed, indicating the flexibility of the model’s applications.

A MINLP model for the layout design of subsea oil gathering - transportation system in deep water oil field considering avoidance of subsea obstacles and pipe intersections - Cheng Hong; Yuxi Wang; Segen F. Estefen (Ocean Engineering, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Parameters for the depth of the ocean’s productive layer - John F. Marra; W. Sean Chamberlin; Carol A. Knudson; W. Joseph Rhea; Cheng Ho (Frontiers in Marine Science, 2023)
Here we compare various parameters that are used to define the depth of the ocean’s productive layer, the euphotic zone, during the initiation of the spring phytoplankton bloom in the North Atlantic (47°N/20°W). These are (1) the compensation depth ( Zc , where gross photosynthesis balances autotrophic respiration), (2) the depth horizon of 1% of surface photosynthetic active irradiance (Ed(0 - ,PAR), (3) depth horizon of 1% of surface Ed(488), and (4) the depth of the bottom of the fluorescence maximum. We also use two related parameters, the depth of the mixed layer and the ratio of integral gross production to integral respiration as a scaling factor for a proxy for the critical depth. Over the course of the observational period (25 April - 7 May, 1989), the mixed layer decreased from 162 to 20 m, and Zc decreased from 64 to 35 m. The depth of 1%Ed(0 - ,PAR) followed the trajectory of Zc , while Ed(488) and the depth of the bottom of the fluorescence maximum were about 10 m deeper, on average. These data support the criterion of the depth of “1%PAR” to describe the productive layer for more productive areas of the ocean. However, 1% of Ed(488) or the bottom of the fluorescence maximum could be used over a broader range of trophic conditions.

Extracellular vesicles with diagnostic and therapeutic potential for prion diseases - Arun Khadka; Jereme G. Spiers; Lesley Cheng; Andrew F. Hill (Cell and Tissue Research, 2023)
Prion diseases (PrD) or transmissible spongiform encephalopathies (TSE) are invariably fatal and pathogenic neurodegenerative disorders caused by the self-propagated misfolding of cellular prion protein (PrP C ) to the neurotoxic pathogenic form (PrP TSE ) via a yet undefined but profoundly complex mechanism. Despite several decades of research on PrD, the basic understanding of where and how PrP C is transformed to the misfolded, aggregation-prone and pathogenic PrP TSE remains elusive. The primary clinical hallmarks of PrD include vacuolation-associated spongiform changes and PrP TSE accumulation in neural tissue together with astrogliosis. The difficulty in unravelling the disease mechanisms has been related to the rare occurrence and long incubation period (over decades) followed by a very short clinical phase (few months). Additional challenge in unravelling the disease is implicated to the unique nature of the agent, its complexity and strain diversity, resulting in the heterogeneity of the clinical manifestations and potentially diverse disease mechanisms. Recent advances in tissue isolation and processing techniques have identified novel means of intercellular communication through extracellular vesicles (EVs) that contribute to PrP TSE transmission in PrD. This review will comprehensively discuss PrP TSE transmission and neurotoxicity, focusing on the role of EVs in disease progression, biomarker discovery and potential therapeutic agents for the treatment of PrD.

Deciphering Alternaria metabolic responses in microbial confrontation via an integrated mass spectrometric targeted and non-targeted strategy - Ye Tian; Mohamed F. Abdallah; Marthe De Boevre; Kris Audenaert; Cheng Wang; Sarah De Saeger; Aibo Wu (Food Chemistry, 2023)

Transition from tholeiitic to alkali basalts via interaction between decarbonated eclogite-derived melts and peridotite - Qiuhong Xie; Zhaochong Zhang; Stephen F. Foley; Chunfei Chen; Zhiguo Cheng; Yu Wang; Weiliang Kong; Yiwen Lv; M. Santosh; Qizhen Jin; Lukáš Krmíček; Xiangkun Zhu (Chemical Geology, 2023)

Quantifying long‐term phenological patterns of aerial insectivores roosting in the Great Lakes region using weather surveillance radar - Yuting Deng; Maria Carolina T. D. Belotti; Wenlong Zhao; Zezhou Cheng; Gustavo Perez; Elske Tielens; Victoria F. Simons; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Change Biology, 2023)
Organisms have been shifting their timing of life history events (phenology) in response to changes in the emergence of resources induced by climate change. Yet understanding these patterns at large scales and across long time series is often challenging. Here we used the US weather surveillance radar network to collect data on the timing of communal swallow and martin roosts and evaluate the scale of phenological shifts and its potential association with temperature. The discrete morning departures of these aggregated aerial insectivores from ground‐based roosting locations are detected by radars around sunrise. For the first time, we applied a machine learning algorithm to automatically detect and track these large‐scale behaviors. We used 21 years of data from 12 weather surveillance radar stations in the Great Lakes region to quantify the phenology in roosting behavior of aerial insectivores at three spatial levels: local roost cluster, radar station, and across the Great Lakes region. We show that their peak roosting activity timing has advanced by 2.26 days per decade at the regional scale. Similar signals of advancement were found at the station scale, but not at the local roost cluster scale. Air temperature trends in the Great Lakes region during the active roosting period were predictive of later stages of roosting phenology trends (75% and 90% passage dates). Our study represents one of the longest‐term broad‐scale phenology examinations of avian aerial insectivore species responding to environmental change and provides a stepping stone for examining potential phenological mismatches across trophic levels at broad spatial scales.

Experimental observation and geophysical modeling of the hydrological effects on Pleistocene glaciation deposits susceptible to landslide - L.-J. Su; F. Ullah; S. Ali; L. Cheng; M. Ur Rehman; M. Alam (International Journal of Environmental Science and Technology, 2023)

Inferences of waste management policy and reduction of marine debris in Southern Taiwan - H.-T. Yang; H.-R. Chao; Y.-F. Cheng (International Journal of Environmental Science and Technology, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Shear Modulus of a Carbonate Sand–Silt Mixture with THF Hydrate - Yuzhe Ren; C. F. Chiu; Lu Ma; Y. P. Cheng; Litong Ji; Chao Jiang (Journal of Marine Science and Engineering, 2022)
The maximum shear modulus (Gmax) is an important factor determining soil deformation, and it is closely related to engineering safety and seafloor stability. In this study, a series of bender element tests was carried out to investigate the Gmax of a hydrate-bearing carbonate sand (CS)–silt mixture. The soil mixture adopted a CS:silt ratio of 1:4 by weight to mimic the fine-grained deposit of the South China Sea (SCS). Tetrahydrofuran (THF) was used to form the hydrate. Special specimen preparation procedures were adopted to form THF hydrate inside the intraparticle voids of the CS. The test results indicate that hydrate contributed to a significant part of the skeletal stiffness of the hydrate-bearing CS–silt mixture, and its Gmax at 5% hydrate saturation (Sh) was 4–6 times that of the host soil mixture. Such stiffness enhancement at a low Sh may be related to the cementation hydrate morphology. However, the Gmax of the hydrate-bearing CS–silt mixture was also sensitive to the effective stress for an Sh ranging between 5% and 31%, implying that the frame-supporting hydrate morphology also plays a key role in the skeletal stiffness of the soil mixture. Neither the existing cementation models nor the theoretical frame-supporting (i.e., Biot–Gassmann theory by Lee (BGTL)), could alone provide a satisfactory prediction of the test results. Thus, further theoretical study involving a combination of cementation and frame-supporting models is essential to understand the effects of complicated hydrate morphologies on the stiffness of soil with a substantial amount of intraparticle voids.

A systematic review and meta-analysis of non-vitamin K antagonist oral anticoagulants vs vitamin K antagonists after transcatheter aortic valve replacement in patients with atrial fibrillation - Amanda Jia Qi Ooi; Chloe Wong; Timothy Wei Ern Tan; Trina Priscilla Ng; Yao Neng Teo; Yao Hao Teo; Nicholas L. Syn; Andie H. Djohan; Yinghao Lim; Leonard L. L. Yeo; Benjamin Y. Q. Tan; Mark Yan-Yee Chan; et al. (European Journal of Clinical Pharmacology, 2022)

Dust control performance enhancement of red sand via the synergistic application of Na- and Ca-lignosulfonates - X. Ding; Z. Luo; F. Cheng; J. Deng (International Journal of Environmental Science and Technology, 2022)

Neuroparsin 1 (MrNP1) and Neuroparsin 2 (MrNP2) Are Involved in the Regulation of Vitellogenesis in the Shrimp Macrobrachium rosenbergii - Chun Mei Ao; Li Li Shi; Wei Wang; Cheng Gui Wang; Siuming F. Chan (Frontiers in Marine Science, 2022)
Neuroparsins (NP) are small-size cysteine-rich neuropeptides first discovered in insects. They are known to be involved in insect reproduction. In this study, we have cloned two neuroparsin cDNAs (i.e., MrNP1 and MrNP2) from the freshwater shrimp Macrobrachium rosenbergii . The two neuroparsins consist of 12 cysteines, which is characteristic of the neuroparsin family. These cysteines are arranged in identical relative positions that form 6-disulfide bonds. MrNP1 and MrNP2 are most similar to the corresponding neuroparsin counterparts of the shrimp Macrobrachium nipponense . Phylogenetic study results suggested that MrNP1 and MrNP2 are closely related to MnNP1 and MnNP3, respectively. Also, an additional MrNP gene similar to MnNP2 is expected to exist in M. rosenbergii. The MrNP1 expression level is the highest in the ovary, and MrNP2 expression is higher in the brain and heart of the females. In addition, during the ovary maturation cycle, MrNP1 expression in the hepatopancreas is highest in stage V; in the ovary it is variable. MrNP2 expression in the hepatopancreas and ovary is the highest in stage II and stage I, respectively. In vivo and in vitro bioassay experiment results indicate that MrNP1 and MrNP2 recombinant proteins can stimulate the expression of the MrVg gene. In contrast, silencing of MrNP1 and MrNP2 genes would suppress MrVg, VgR, and CyclinB gene expressions. The results indicate that the products of both genes can stimulate vitellogenesis by up-regulating the MrVg gene expression. Results from their difference in expression patterns indicate that they might have different regulatory roles in vitellogenin synthesis. Since gene silencing of either MrNP1 or MrNP2 affected the expression of the other NP, we have hypothesized that coordinated regulatory action between MrNP1 and MrNP2 may be necessary for the normal vitellogenesis in M. rosenbergii.

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Alternative Splicing of the Lobster (Homarus americanus) Crustacean Hyperglycemic Hormone A and B Genes Produce 2 Protein Variants Involved in Vitellogenin Inhibition - Cheng Gui Wang; Wei Wang; Li Li Shi; Yu Chun Shen; Siuming F. Chan (Frontiers in Marine Science, 2022)
Current BLASTP search analysis results suggested that the lobster ( Homarus americanus ) HaCHH-A and HaCHH-B may be derived from two different four-exon genes. Repeated tissue expression studies have revealed much different expression patterns of these two genes from those reported in the past. With RT-PCR, rapid amplification of complementary DNA (cDNA) ends (RACE), and genomic DNA cloning, we confirmed that the HaCHH-A and HaCHH-B transcripts were derived from two different four-exon CHH genes. By an alternative splicing mechanism, each gene can produce different but larger transcript variants (i.e., sHaCHH-A and sHaCHH-B ) mainly in different non-eyestalk tissues of the females. The larger and unspliced transcripts can be detected in the hepatopancreas, gill, heart, nerve cord, brain, ovary, and thoracic ganglion of the reproductive females. The expression patterns of sHaCHH-A and sHaCHH-B in other non-eyestalk tissues suggest that these transcripts have a wide spectrum of expressions during the female reproductive cycle. An in vitro organ explant culture system was developed to investigate the reproductive function of these cDNAs. The results showed that the recombinant proteins for sHaCHH-A and sHaCHH-B inhibited the gene expression of vitellogenin, whereas the double-stranded RNA (dsRNA) for sHaCHH-A and sHaCHH-B stimulated the expression of the vitellogenin gene in vitro . The results of the study may provide insights for the development of techniques to induce gonad development without using eyestalk ablation operation. This is the first in-depth report of the characterization of two four-exon CHH genes in a crustacean.

Demonstration of a three-dimensional dynamically adaptive atmospheric dynamic framework for the simulation of mountain waves - J. Li; F. Fang; J. Steppeler; J. Zhu; Y. Cheng; X. Wu (Meteorology and Atmospheric Physics, 2021)

Correction to: Extracellular Microvesicles Released From Brain Endothelial Cells are Detected in Animal Models Of HIV‑1 Signifying Unresolved Inflammation - Servio H. Ramirez; Tetyana P. Buzhdygan; Jonathan F. Hale; Liang Cheng; Guangming Li; Bryson Hoover‑Hankerson; Roshanak Razmpour; Uma Sriram; Lishan Su; Raghava Potula; Allison M. Andrews (Journal of Neuroimmune Pharmacology, 2021)

Extracellular Microvesicles Released From Brain Endothelial Cells are Detected in Animal Models Of HIV-1 Signifying Unresolved Inflammation - Servio H. Ramirez; Tetyana P. Buzhdygan; Jonathan F. Hale; Liang Cheng; Guangming Li; Bryson Hoover-Hankerson; Roshanak Razmpour; Uma Sriram; Lishan Su; Raghava Potula; Allison M. Andrews (Journal of Neuroimmune Pharmacology, 2021)
Treatment of HIV-infected patients with antiretroviral therapy (ART) has effectively suppressed viral replication; however, the central nervous system is still a major target and reservoir of the virus leading to the possible development of HIV-associated neurocognitive disorders (HAND). Furthermore, a hallmark feature of HAND is the disruption of the blood–brain barrier that leads to loss of tight junction protein (TJP) complexes. Extracellular vesicles (EVs), released by every cell type in the body, occur in greater quantities in response to cellular activation or injury. We have found that inflammatory insults activate brain endothelial cells (EC) and induce the release of EVs containing TJPs such as Occludin. We thus hypothesized that HIV infection and unresolved neuroinflammation will result in the release of brain-EC derived EVs. Herein, our results show elevated levels of brain-EC EVs in a humanized mouse model of HIV infection. Furthermore, while ART reduced brain-EC EVs, it was unable to completely resolve increased vesicles detectable in the blood. In addition to inflammatory insults, HIV-1 viral proteins (Tat and gp120) increased the release of Occludin + vesicles from human brain microvasculature ECs. This increase in vesicle release could be prevented by knock-down of the small GTPase ARF6. ARF6 has been shown to regulate EV biogenesis in other cell types, and we provide further evidence for the involvement of ARF6 in brain EC derived EVs. Overall, this study offers insight into the process of brain vascular remodeling (via EVs) in the setting of neuroinflammation and thus provides possibilities for biomarker monitoring and targeting of ARF6. Graphical abstract

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Correction to: Chemical Speciation and Interaction Mechanism of U in “Shewanella putrefaciens-Mineral-U” System - J. Gao; W. Yuan; J. Cheng; J. Zhang; S. Feng; F. Huang; F. Yi; H. Huang; H. Zhang (Water, Air, & Soil Pollution, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

Associations of Blood Pressure and Carotid Flow Velocity with Brain Volume and Cerebral Small Vessel Disease in a Community-Based Population - Shao-Yuan Chuang; Pei-Ning Wang; Liang-Kung Chen; Kun-Hsien Chou; Chih-Ping Chung; Chen-Huan Chen; Gary F. Mitchell; Wen-Harn Pan; Hao-Min Cheng (Translational Stroke Research, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

Neuronal Protein Farnesylation Regulates Hippocampal Synaptic Plasticity and Cognitive Function - Wenhui Qu; Kiall F. Suazo; Wenfeng Liu; Shaowu Cheng; Angela Jeong; David Hottman; Li-Lian Yuan; Mark D. Distefano; Ling Li (Molecular Neurobiology, 2021)

The nearly complete mitogenome of the Southeast Asian firefly Pteroptyx tener (Coleoptera: Lampyridae) - S. Cheng; M. N. Mat-Isa; I. S. Sapian; S. F. Ishak (Molecular Biology Reports, 2021)

Effects of some parameters on the removal of Cd(II) ions from aqueous solutions by polyethyleneimine–sodium xanthogenate - G. Wang; X. L. Cheng; Y. C. Zeng; Y. F. Jiang (International Journal of Environmental Science and Technology, 2020)

A robust relationship between multidecadal global warming rate variations and the Atlantic Multidecadal Variability - Zhiyu Li; Wenjun Zhang; Fei-Fei Jin; Malte F. Stuecker; Cheng Sun; Aaron F. Z. Levine; Haiming Xu; Chao Liu (Climate Dynamics, 2020)

Intercomparison of Large-Eddy Simulations of the Antarctic Boundary Layer for Very Stable Stratification - Fleur Couvreux; Eric Bazile; Quentin Rodier; Björn Maronga; Georgios Matheou; Maria J. Chinita; John Edwards; Bart J. H. van Stratum; Chiel C. van Heerwaarden; Jing Huang; Arnold F. Moene; Anning Cheng; et al. (Boundary-Layer Meteorology, 2020)

Jurassic uplift and erosion of the northeast Queensland continental margin: evidence from (U–Th)/He thermochronology combined with U–Pb detrital zircon age spectra - Y. Cheng; C. N. Todd; R. A. Henderson; M. Danišík; F. Sahlström; Z. Chang; I. Corral (Australian Journal of Earth Sciences, 2020)

A comparison of regional brain volumes and white matter connectivity in subjects with stimulant induced psychosis versus schizophrenia - Peter D. Alexander; Kristina M. Gicas; Alex Cheng; Donna J. Lang; Ric M. Procyshyn; Alexandra T. Vertinsky; William J. Panenka; Allen E. Thornton; Alexander Rauscher; Jamie Y. X. Wong; Tasha Chan; Andrea A. Jones; et al. (Psychopharmacology, 2019)

Hip Fracture Discrimination Based on Statistical Multi-parametric Modeling (SMPM) - Julio Carballido-Gamio; Aihong Yu; Ling Wang; Yongbin Su; Andrew J. Burghardt; Thomas F. Lang; Xiaoguang Cheng (Annals of Biomedical Engineering, 2019)

Observational Needs Supporting Marine Ecosystems Modeling and Forecasting: From the Global Ocean to Regional and Coastal Systems - Antonietta Capotondi; Michael Jacox; Chris Bowler; Maria Kavanaugh; Patrick Lehodey; Daniel Barrie; Stephanie Brodie; Samuel Chaffron; Wei Cheng; Daniela F. Dias; Damien Eveillard; Lionel Guidi; et al. (Frontiers in Marine Science, 2019)

POD characterisation of extreme wake patterns of turbulent wind fields past rectangular buildings - F. Wang; L. Cheng; K. M. Lam (Environmental Fluid Mechanics, 2019)

Molecular characterization of heat shock protein 90 from the dinoflagellate Prorocentrum donghaiense and its transcriptional response to thermal, copper and nutrient stresses - Chun Y. Zhang; Guo F. Chen; Yuan Y. Wang; Xu D. Zhang; Cheng H. Li (Marine Biology Research, 2019)

Preparation and DEA removal performance of iron-modified activated carbon - H. Li; F. Cui; F. Zhang; J. Cui; Q. Meng; J. Cheng (International Journal of Environmental Science and Technology, 2019)

Effects of law enforcement and community outreach on mammal diversity in a biodiversity hotspot - Cheng Chen; Rui‐Chang Quan; Guanghong Cao; Hongpei Yang; A. Cole Burton; Michael Meitner; Jedediah F. Brodie (Conservation Biology, 2019)
Management activities such as law enforcement and community outreach are thought to affect conservation outcomes in protected areas, but their importance relative to intrinsic environmental characteristics of the parks and extrinsic human pressures surrounding the parks have not been explored. Furthermore, it is not clear which is more related to conservation outcomes—the management itself or local people's perceptions of the management. We measured objective (reports by park staff) and subjective (reports by local people) levels of community outreach and law enforcement based on responses to 374 questionnaires. We estimated mammal abundance and diversity of 6 protected areas based on data from 115 camera traps in Xishuangbanna, southwest China, a biodiversity hotspot with high hunting and land‐conversion pressures. We then examined correlations among them and found that local people's perception of law enforcement was positively related to the local abundance of 2 large, hunted species, wild boar ( Sus scrofa ) (β = 15.22) and muntjac ( Muntiacus vaginalis ) (β = 14.82), but not related to the abundance of smaller mammals or to objective levels of enforcement. The subjective frequency of outreach by park staff to local communities (β = 3.42) and park size (β = 3.28) were significantly and positively related to mammal species richness, whereas elevation, human population density, and subjective frequency of law enforcement were not. We could not conclude that community outreach and law enforcement were directly causing increased mammal abundance and diversity. Nevertheless, the patterns we detected are some of the first empirical evidence consistent with the idea that biodiversity in protected areas may be more positively and strongly related to local perceptions of the intensity of park management than to either intrinsic (e.g., elevation, park size) or extrinsic (e.g., human population density) environmental factors.

Differentiations of geographic distribution and subsistence strategies between Tibetan and other major ethnic groups are determined by the physical environment in Hehuang Valley - Xin Jia; Harry F. Lee; Mengchun Cui; Guoquan Cheng; Yang Zhao; Hong Ding; Ricci P. H. Yue; Huayu Lu (Science China Earth Sciences, 2019)

Amyloid Precursor Protein Dimerisation Reduces Neurite Outgrowth - Luan Luu; Giuseppe D. Ciccotosto; Laura J. Vella; Lesley Cheng; Laila C. Roisman; Gerhard Multhaup; Andrew F. Hill; Lisa-Marie Munter; Roberto Cappai (Molecular Neurobiology, 2019)

Identification of major insect pests of Amaranthus spp. and germplasm screening for insect resistance in Tanzania - Jason D. Smith; Fekadu F. Dinssa; Robert S. Anderson; Fu-cheng Su; Ramasamy Srinivasan (International Journal of Tropical Insect Science, 2018)

Effects of Modified Palygorskite Supplementation on Egg Quality and Mineral Element Content, and Intestinal Integrity and Barrier Function of Laying Hens - Y. Su; Y. P. Chen; Y. F. Cheng; C. Wen; Y. M. Zhou (Biological Trace Element Research, 2018)

A Physiological/Model Study on the Effects of Deep Breathing on the Respiration Rate, Oxygen Saturation, and Cerebral Oxygen Delivery in Humans - K. S. Cheng; P. F. Lee (Neurophysiology, 2018)

Genomic characterizations of H4 subtype avian influenza viruses from live poultry markets in Sichuan province of China, 2014–2015 - Chuansong Quan; Ting Huang; Xiuwei Chen; Jie Zhang; Qianli Wang; Cheng Zhang; Tiyan Zhang; Lijun Zhou; Liumei Shu; Chunrong Long; Lei Yang; Xunbo Du; et al. (Science China Life Sciences, 2018)

Bacteria and viruses in the nasopharynx immediately prior to onset of acute lower respiratory infections in Indigenous Australian children - Heidi C. Smith-Vaughan; Michael J. Binks; Jemima Beissbarth; Anne B. Chang; Gabrielle B. McCallum; Ian M. Mackay; Peter S. Morris; Robyn L. Marsh; Paul J. Torzillo; Danielle F. Wurzel; Keith Grimwood; Elizabeth Nosworthy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Characterization and virus susceptibility of a continuous cell line derived from the brain of Aequidens rivulatus (Günther) - S W Yeh; Y H Cheng; F N Nan; C M Wen (Journal of Fish Diseases, 2018)
Cell cultures derived from the brain tissues of Aequidens rivulatus (Günther) have been characterized previously. In this study, a continuous cell line ARB 8 was further established, and its growth characteristics, transcription and susceptibility to fish viruses—including chum salmon reovirus ( CSV ), marbled eel infectious pancreative necrosis virus ( MEIPNV ), grouper nervous necrosis virus ( GNNV ), giant seaperch iridovirus ( GSIV ), red seabream iridovirus ( RSIV ), koi herpesvirus ( KHV ), herpesvirus anguilla ( HVA ) and marbled eel polyoma‐like virus ( MEP yV)—were examined. ARB 8 cells that showed epithelioid morphology and were passaged >80 times grew well at temperatures ranging from 25°C to 30°C in L‐15 medium containing 5%–15% foetal bovine serum. The cells constitutively transcribed connexion 43, glutamine synthetase, nestin and nkx6‐2, which are markers for neural progenitor cells. The cells were highly susceptible to CSV , MEIPNV , GSIV and RSIV and showed the typical cytopathic effect ( CPE ). However, the cells were resistant to GNNV , KHV , HVA and MEP yV because no significant CPE was noted after infection. Optimal temperatures for virus production ranged from 25°C to 30°C. The results revealed that the neural progenitor cell line ARB 8 can potentially serve as a useful tool for investigating fish viruses and isolating new viruses in ornamental cichlid fishes.

Phage Application for the Protection from Acute Hepatopancreatic Necrosis Disease (AHPND) in Penaeus vannamei - Jin Woo Jun; Jee Eun Han; Sib Sankar Giri; Kathy F. J. Tang; Xiaohui Zhou; Luis Fernando Aranguren; Hyoun Joong Kim; Saekil Yun; Cheng Chi; Sang Guen Kim; Se Chang Park (Indian Journal of Microbiology, 2018)

Evaluation of Dietary Palygorskite Supplementation on Growth Performance, Mineral Accumulations, Antioxidant Capacities, and Meat Quality of Broilers Fed Lead-Contaminated Diet - Y. F. Cheng; Y. P. Chen; C. Wen; W. B. Wang; A. Q. Wang; Y. M. Zhou (Biological Trace Element Research, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Serum 25-hydroxyvitamin D concentrations and lung cancer risk in never-smoking postmenopausal women - Ting-Yuan David Cheng; Xiaoling Song; Shirley A. A. Beresford; Gloria Y. F. Ho; Karen C. Johnson; Mridul Datta; Rowan T. Chlebowski; Jean Wactawski-Wende; Lihong Qi; Marian L. Neuhouser (Cancer Causes & Control, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Molecular characterization of two Rhesus glycoproteins from the euryhaline freshwater white-rimmed stingray, Himantura signifer, and changes in their transcript levels and protein abundance in the gills, kidney, and liver during brackish water acclimation - Cheng T. Yeam; You R. Chng; Jasmine L. Y. Ong; Wai P. Wong; Shit F. Chew; Yuen K. Ip (Journal of Comparative Physiology B, 2017)

Utilizing secondary agricultural education programs to deliver evidence-based grain safety training for young and beginning workers - Yuan-Hsin Cheng; William E Field; Roger L Tormoehlen; Brian F French (Journal of Agromedicine, 2017)

Lipid emulsion enhances cardiac performance after ischemia–reperfusion in isolated hearts from summer-active arctic ground squirrels - Michele M. Salzman; Qunli Cheng; Richard J. Deklotz; Gurpreet K. Dulai; Hunter F. Douglas; Anna E. Dikalova; Dorothee Weihrauch; Brian M. Barnes; Matthias L. Riess (Journal of Comparative Physiology B, 2017)

Dalbavancin reduces biofilms of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE) - D. Knafl; S. Tobudic; S. C. Cheng; D. R. Bellamy; F. Thalhammer (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Metastatic melanoma moves on: translational science in the era of personalized medicine - Mitchell P. Levesque; Phil F. Cheng; Marieke I.G. Raaijmakers; Annalisa Saltari; Reinhard Dummer (Cancer and Metastasis Reviews, 2017)

Pathogen dynamics during invasion and establishment of white‐nose syndrome explain mechanisms of host persistence - Winifred F. Frick; Tina L. Cheng; Kate E. Langwig; Joseph R. Hoyt; Amanda F. Janicki; Katy L. Parise; Jeffrey T. Foster; A. Marm Kilpatrick (Ecology, 2017)
Disease dynamics during pathogen invasion and establishment determine the impacts of disease on host populations and determine the mechanisms of host persistence. Temporal progression of prevalence and infection intensity illustrate whether tolerance, resistance, reduced transmission, or demographic compensation allow initially declining populations to persist. We measured infection dynamics of the fungal pathogen Pseudogymnoascus destructans that causes white‐nose syndrome in bats by estimating pathogen prevalence and load in seven bat species at 167 hibernacula over a decade as the pathogen invaded, became established, and some host populations stabilized. Fungal loads increased rapidly and prevalence rose to nearly 100% at most sites within 2 yr of invasion in six of seven species. Prevalence and loads did not decline over time despite huge reductions in colony sizes, likely due to an extensive environmental reservoir. However, there was substantial variation in fungal load among sites with persisting colonies, suggesting that both tolerance and resistance developed at different sites in the same species. In contrast, one species disappeared from hibernacula within 3 yr of pathogen invasion. Variable host responses to pathogen invasion require different management strategies to prevent disease‐induced extinction and to facilitate evolution of tolerance or resistance in persisting populations.

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

Hong Kong’s rich marine biodiversity: the unseen wealth of South China’s megalopolis - Terence P. T. Ng; Martin C. F. Cheng; Kevin K. Y. Ho; Gilbert C. S. Lui; Kenneth M. Y. Leung; Gray A. Williams (Biodiversity and Conservation, 2017)

Microglia Activation and Polarization After Intracerebral Hemorrhage in Mice: the Role of Protease-Activated Receptor-1 - Shu Wan; Yingying Cheng; Hang Jin; Dewei Guo; Ya Hua; Richard F. Keep; Guohua Xi (Translational Stroke Research, 2016)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

Effects of Palygorskite Inclusion on the Growth Performance, Meat Quality, Antioxidant Ability, and Mineral Element Content of Broilers - Y. F. Cheng; Y. P. Chen; X. H. Li; W. L. Yang; C. Wen; Y. M. Zhou (Biological Trace Element Research, 2016)

G protein-coupled estrogen receptor inhibits the P2Y receptor-mediated Ca2+ signaling pathway in human airway epithelia - Yuan Hao; Alison W. Chow; Wallace C. Yip; Chi H. Li; Tai F. Wan; Benjamin C. Tong; King H. Cheung; Wood Y. Chan; Yangchao Chen; Christopher H. Cheng; Wing H. Ko (Pflügers Archiv - European Journal of Physiology, 2016)

Toxicity and in vitro activity of HIV-1 latency-reversing agents in primary CNS cells - Lachlan R. Gray; Hung On; Emma Roberts; Hao K. Lu; Michael A. Moso; Jacqueline A. Raison; Catherine Papaioannou; Wan-Jung Cheng; Anne M. Ellett; Jonathan C. Jacobson; Damian F. J. Purcell; Steve L. Wesselingh; et al. (Journal of NeuroVirology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Contrasting effects of organic amendments on phytoextraction of heavy metals in a contaminated sediment - Chengjun Zhang; Gary J. Clark; Antonio F. Patti; Nanthi Bolan; Miaomiao Cheng; Peter W. G. Sale; Caixian Tang (Plant and Soil, 2015)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Use of fluoroquinolones is the single most important risk factor for the high bacterial load in patients with nasal and gastrointestinal colonization by multidrug-resistant Acinetobacter baumannii - V. C. C. Cheng; J. H. K. Chen; S. Y. C. So; S. C. Y. Wong; M. K. Yan; P. H. Chau; W. M. Lee; K. K. W. To; J. F. W. Chan; I. F. N. Hung; P. L. Ho; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

White matter abnormalities of microstructure and physiological noise in schizophrenia - Hu Cheng; Sharlene D. Newman; Jerillyn S. Kent; Amanda Bolbecker; Mallory J. Klaunig; Brian F. O’Donnell; Aina Puce; William P. Hetrick (Brain Imaging and Behavior, 2015)

Use of food waste as fish feeds: effects of prebiotic fibers (inulin and mannanoligosaccharide) on growth and non-specific immunity of grass carp (Ctenopharyngodon idella) - Wing Y. Mo; Zhang Cheng; Wai M. Choi; Clare H. I. Lun; Yu B. Man; James T. F. Wong; Xun W. Chen; Stanley C. K. Lau; Ming H. Wong (Environmental Science and Pollution Research, 2015)

Global diversity and taxonomy of the Auricularia auricula-judae complex (Auriculariales, Basidiomycota) - Fang Wu; Yuan Yuan; Shuang-Hui He; Asanka R. Bandara; Kevin D. Hyde; Vera F. Malysheva; De-Wei Li; Yu-Cheng Dai (Mycological Progress, 2015)

Identification and characterization of a late gene encoded by grouper iridovirus 2L (GIV‐2L) - H‐Y Lin; C‐F Cheng; P P Chiou; C‐J Liou; J‐C Yiu; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) belongs to the Ranavirus genus and is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. In this study, we identified and characterized the GIV‐2L gene, which encodes a protein of unknown function. GIV‐2L is 1242 bp in length, with a predicted protein mass of 46.2 kDa. It displayed significant identity only with members of the Ranavirus and Iridovirus genera. We produced mouse monoclonal antibodies against the GIV‐2L protein by immunizing mice with GIV‐2L‐His‐tag recombinant protein. By inhibiting de novo protein and DNA synthesis in GIV‐infected cells, we showed that GIV‐2L was a late gene during the viral replication. Finally, immunofluorescence microscopy revealed that GIV‐2L protein accumulated in both the nucleus and cytoplasm of infected cells. These results offer important insights into the pathogenesis of GIV.

Chemicals to induce plastid signals in Arabidopsis seedlings - Z.-W. Zhang; F. Wu; J. Cheng; M. Yuan; Y.-E. Chen; D.-W. Zhang; F. Zhu; S. Yuan (Plant Biosystems, 2015)

Recent climate warming favours more specialized cladoceran taxa in western Canadian Arctic lakes - Joshua R. Thienpont; Jennifer B. Korosi; Elisa S. Cheng; Kayla Deasley; Michael F. J. Pisaric; John P. Smol (Journal of Biogeography, 2015)
Aim Shifts in the distribution of freshwater algal communities as a result of climate‐related limnological changes are well documented; however, impacts on higher trophic levels have received less attention. For example, little is known about how Cladocera (Crustacea, Branchiopoda), often dominant invertebrates and key ecological indicators, have responded to recent warming on broad spatial and temporal scales. Here, we use lake sediment records to test the hypothesis that recent, intensive warming in the western Canadian Arctic has resulted in consistent shifts in the composition of cladoceran assemblages. Location Small, first‐order lakes in the Mackenzie Delta region of the western Canadian Arctic. Methods Sediment cores representing the recent past (approximately 150–200 years) were obtained from five lakes spanning a strong climatic gradient. Subfossil remains of Cladocera were identified and enumerated and overall primary production was inferred using spectroscopic techniques. The habitat preferences and feeding strategy of each taxon were compared. Detrended canonical correspondence analysis was used to estimate compositional turnover since 1850, and compared with that of three cladoceran assemblages from Nova Scotia, to place high‐latitude changes in context. Results Cladoceran assemblage changes occurred coincident with the timing of known regional warming and were strongly linked to estimated changes in primary production. In the northern and deepest lakes, an increase in the planktonic, filter‐feeding taxon Bosmina spp. coincided with a decrease in the generalist littoral taxa Chydorus cf. brevilabris and Alona circumfimbriata . In the more southern lakes, an increase in macrophyte‐associated scrapers Acroperus harpae and Eurycercus spp. occurred concurrently with decreases in generalist taxa. In one lake, an increase in another specialist, an obligate mud‐dwelling taxon, was observed. Main conclusions In the western Canadian Arctic, warming has resulted in an increase in cladoceran taxa occupying more specialized feeding and habitat niches. Generalist taxa capable of occupying multiple habitats and employing diverse feeding strategies have been systematically replaced by more specialist species. This response is analogous to what has been inferred for algal communities across the Northern Hemisphere, and represents the first evidence of consistent cladoceran changes to recent climate warming in high‐latitude regions.

Containment of Clostridium difficile infection without reduction in antimicrobial use in Hong Kong - V. C. C. Cheng; P. H. Chau; S. Y. C. So; J. H. K. Chen; R. W. S. Poon; S. C. Y. Wong; I. F. N. Hung; W. M. Lee; J. W. M. Tai; P. L. Ho; W. C. Yam; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Assessing the genetic diversity and resistance to Cucumber mosaic virus and Tobacco etch virus of tobacco cultivars in China - W. Chen; Z. P. Luo; W. T. Liu; H. Liu; D. F. Ma; J. H. Snyder; X. Li; T. Huang; J. L. Cheng; X. Xie; Y. F. Wu (Australasian Plant Pathology, 2015)

Online monitoring of the nanoscale zero-valent iron process for trichloroethylene wastewater treatment - R.-F. Yu; F.-H. Chi; W.-P. Cheng; M.-H. Wang (International Journal of Environmental Science and Technology, 2015)

The RIG-I-like helicase receptor MDA5 (IFIH1) is involved in the host defense against Candida infections - M. Jaeger; R. van der Lee; S.-C. Cheng; M. D. Johnson; V. Kumar; A. Ng; T. S. Plantinga; S. P. Smeekens; M. Oosting; X. Wang; W. Barchet; K. Fitzgerald; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Control of hospital endemicity of multiple-drug-resistant Acinetobacter baumannii ST457 with directly observed hand hygiene - V. C. C. Cheng; J. H. K. Chen; R. W. S. Poon; W. M. Lee; S. Y. C. So; S. C. Y. Wong; P. H. Chau; C. C. Y. Yip; S. S. Y. Wong; J. F. W. Chan; I. F. N. Hung; P. L. Ho; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Ecological functions of uncultured microorganisms in the cobalt-rich ferromanganese crust of a seamount in the central Pacific are elucidated by fosmid sequencing - Yingyi Huo; Hong Cheng; Anton F. Post; Chunsheng Wang; Xiawei Jiang; Jie Pan; Min Wu; Xuewei Xu (Acta Oceanologica Sinica, 2015)

Stress response of Chlorella pyrenoidosa to nitro-aromatic compounds - Chang Xu; Ruihua Wang; Y. F. Zhang; P. Cheng; Martin M. F. Choi; Karen Poon (Environmental Science and Pollution Research, 2015)

Effects of water quality of the basin caused by nitrogen loss from soil in drought - B. B. Huang; D. H. Yan; H. Wang; B. F. Cheng; X. H. Cui (Natural Hazards, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

The Effects of Oxidative Stress on the Compressive Damage Thresholds of C2C12 Mouse Myoblasts: Implications for Deep Tissue Injury - Yifei Yao; Zhitao Xiao; Singwan Wong; Yu-Chun Hsu; Truman Cheng; Chih-Chieh Chang; Liming Bian; Arthur F. T. Mak (Annals of Biomedical Engineering, 2015)

Erratum to: On-line evaluating the SS removals for chemical coagulation using digital image analysis and artificial neural networks - R.-F. Yu; W. Wang; W.-P. Cheng; M.-M. Chen (International Journal of Environmental Science and Technology, 2015)

Effects of Five Naturally Occurring Sugars on the Longevity, Oogenesis, and Nutrient Accumulation Pattern in Adult Females of the Synovigenic Parasitoid Neochrysocharis formosa (Hymenoptera: Eulophidae) - W Wang; S-L Lu; W-X Liu; L-S Cheng; Y-B Zhang; F-H Wan (Neotropical Entomology, 2014)

An Experimental Study of Crack Coalescence Behaviour in Rock-Like Materials Containing Multiple Flaws Under Uniaxial Compression - X. P. Zhou; H. Cheng; Y. F. Feng (Rock Mechanics and Rock Engineering, 2014)

Thrombin-Induced Cerebral Hemorrhage: Role of Protease-Activated Receptor-1 - Yingying Cheng; Guohua Xi; Hang Jin; Richard F. Keep; Jiachun Feng; Ya Hua (Translational Stroke Research, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Influence of Unloading Rate on the Strainburst Characteristics of Beishan Granite Under True-Triaxial Unloading Conditions - X. G. Zhao; J. Wang; M. Cai; C. Cheng; L. K. Ma; R. Su; F. Zhao; D. J. Li (Rock Mechanics and Rock Engineering, 2014)

Molecular evidence for co-occurring cryptic lineages within the Sepioteuthis cf. lessoniana species complex in the Indian and Indo-West Pacific Oceans - S. H. Cheng; F. E. Anderson; A. Bergman; G. N. Mahardika; Z. A. Muchlisin; B. T. Dang; H. P. Calumpong; K. S. Mohamed; G. Sasikumar; V. Venkatesan; P. H. Barber (Hydrobiologia, 2014)

Optimism and Challenge for Science‐Based Conservation of Migratory Species in and out of U.S. National Parks - JOEL BERGER; STEVEN L. CAIN; ELLEN CHENG; PETER DRATCH; KEVIN ELLISON; JOHN FRANCIS; HERBERT C. FROST; SCOTT GENDE; CRAIG GROVES; WILLIAM A. KARESH; ELAINE LESLIE; GARY MACHLIS; et al. (Conservation Biology, 2014)
Public agencies sometimes seek outside guidance when capacity to achieve their mission is limited. Through a cooperative agreement and collaborations with the U.S. National Park Service (NPS), we developed recommendations for a conservation program for migratory species. Although NPS manages ∼36 million hectares of land and water in 401 units, there is no centralized program to conserve wild animals reliant on NPS units that also migrate hundreds to thousands of kilometers beyond parks. Migrations are imperiled by habitat destruction, unsustainable harvest, climate change, and other impediments. A successful program to counter these challenges requires public support, national and international outreach, and flourishing migrant populations. We recommended two initial steps. First, in the short term, launch or build on a suite of projects for high‐profile migratory species that can serve as proof to demonstrate the centrality of NPS units to conservation at different scales. Second, over the longer term, build new capacity to conserve migratory species. Capacity building will entail increasing the limited knowledge among park staff about how and where species or populations migrate, conditions that enable migration, and identifying species’ needs and resolving them both within and beyond parks. Building capacity will also require ensuring that park superintendents and staff at all levels support conservation beyond statutory borders. Until additional diverse stakeholders and a broader American public realize what can be lost and do more to protect it and engage more with land management agencies to implement actions that facilitate conservation, long distance migrations are increasingly likely to become phenomena of the past. Optimismo y Retos para la Conservación Científicamente Basada de Especies Migratorias Dentro y Fuera de Parques Nacionales de E.U.A.

Depressed calcium-handling proteins due to endoplasmic reticulum stress and apoptosis in the diabetic heart are attenuated by argirein - F. H. Shi; Y. S. Cheng; D. Z. Dai; H. J. Peng; X. D. Cong; Y. Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Levels, seasonal variations, and health risks assessment of ambient air pollutants in the residential areas - W. C. Zhao; J. P. Cheng; Z. Y. Yu; Q. L. Tang; F. Cheng; Y. W. Yin; W. H. Wang (International Journal of Environmental Science and Technology, 2013)

A radiation hybrid map of chromosome 1D reveals synteny conservation at a wheat speciation locus - Monika K. Michalak de Jimenez; Filippo M. Bassi; Farhad Ghavami; Kristin Simons; Rissa Dizon; Raed I. Seetan; Loai M. Alnemer; Anne M. Denton; Münevver Doğramacı; Hana Šimková; Jaroslav Doležel; Kiran Seth; et al. (Functional & Integrative Genomics, 2013)

Wheat Zapper: a flexible online tool for colinearity studies in grass genomes - Loai M. Alnemer; Raed I. Seetan; Filippo M. Bassi; Charith Chitraranjan; Adam Helsene; Paul Loree; Steve Bou Goshn; Yong Q. Gu; Ming-Cheng Luo; M. Javed Iqbal; Gerard R. Lazo; Anne M. Denton; et al. (Functional & Integrative Genomics, 2013)

Use of a MM5–CAMx–PSAT Modeling System to Study SO2 Source Apportionment in the Beijing Metropolitan Region - Qing Huang; Shuiyuan Cheng; Rhoda E. Perozzi; Edmund F. Perozzi (Environmental Modeling & Assessment, 2012)

βA3/A1-crystallin is required for proper astrocyte template formation and vascular remodeling in the retina - Debasish Sinha; Mallika Valapala; Imran Bhutto; Bonnie Patek; Cheng Zhang; Stacey Hose; Fang Yang; Marisol Cano; Walter J. Stark; Gerard A. Lutty; J. Samuel Zigler; Eric F. Wawrousek (Transgenic Research, 2012)

A path radiance estimation algorithm using reflectance measurements in radiometric control areas - K. S. Cheng; Y. F. Su; H. C. Yeh; J. H. Chang; W. C. Hung (International Journal of Remote Sensing, 2012)

A preliminary study on the molecular evolution of the two routes of intrauterine transmission of HBV - H. Sun; X. Tang; B. Wang; J. Zhang; H. Cheng; H. Su; F. Li; K. Men; S. Wang; L. Zhao; J. Xu; X. Yu; et al. (Archives of Virology, 2012)

Clostridium difficile isolates with increased sporulation: emergence of PCR ribotype 002 in Hong Kong - V. C. C. Cheng; W. C. Yam; O. T. C. Lam; J. L. Y. Tsang; E. Y. F. Tse; G. K. H. Siu; J. F. W. Chan; H. Tse; K. K. W. To; J. W. M. Tai; P. L. Ho; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Chemical Form of Selenium Affects Its Uptake, Transport, and Glutathione Peroxidase Activity in the Human Intestinal Caco-2 Cell Model - Huawei Zeng; Matthew I. Jackson; Wen-Hsing Cheng; Gerald F. Combs (Biological Trace Element Research, 2011)

Comparison of a high-density genetic linkage map to genome features in the model grass Brachypodium distachyon - Naxin Huo; David F. Garvin; Frank M. You; Stephanie McMahon; Ming-Cheng Luo; Yong Q. Gu; Gerard R. Lazo; John Philip Vogel (Theoretical and Applied Genetics, 2011)

Evaluation of the Diurnal Cycle in the Atmospheric Boundary Layer Over Land as Represented by a Variety of Single-Column Models: The Second GABLS Experiment - G. Svensson; A. A. M. Holtslag; V. Kumar; T. Mauritsen; G. J. Steeneveld; W. M. Angevine; E. Bazile; A. Beljaars; E. I. F. de Bruijn; A. Cheng; L. Conangla; J. Cuxart; et al. (Boundary-Layer Meteorology, 2011)

EHPC 2010: sharing knowledge on environmental health for risk mitigation - T. E. Ford; A. L. Bass; S. Cheng; G. N. Cherr; B. Cole; E. Fairbairn; J.-D. Gu; R. S. Halbrook; F. E. Löffler; E. L. Madsen; N. A. McGinn (Ecotoxicology, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Insulin-like growth factor 1 mediates 5-fluorouracil chemoresistance in esophageal carcinoma cells through increasing survivin stability - Hsien-Chia Juan; Hsin-Ting Tsai; Po-Hao Chang; Chi-Ying F. Huang; Cheng-Po Hu; Fen-Hwa Wong (Apoptosis, 2011)

Expression of GDF-9, BMP-15 and their receptors in mammalian ovary follicles - R. Z. Sun; L. Lei; L. Cheng; Z. F. Jin; S. J. Zu; Z. Y. Shan; Z. D. Wang; J. X. Zhang; Z. H. Liu (Journal of Molecular Histology, 2010)

Adventitious shoot regeneration from leaf explants of southern highbush blueberry cultivars - Cheng Liu; Pete Callow; Lisa J. Rowland; James F. Hancock; Guo-qing Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Erratum to: On the relationship between ozone and its precursors in the Pearl River Delta: application of an observation-based model (OBM) - Hairong Cheng; Hai Guo; Xinming Wang; Sam M. Saunders; S. H. M. Lam; Fei Jiang; Tijian Wang; Aijun Ding; Shuncheng Lee; K. F. Ho (Environmental Science and Pollution Research, 2010)

On the relationship between ozone and its precursors in the Pearl River Delta: application of an observation-based model (OBM) - Hairong Cheng; Hai Guo; Xinming Wang; Sam M. Saunders; S. H. M. Lam; Fei Jiang; Tijian Wang; Aijun Ding; Shuncheng Lee; K. F. Ho (Environmental Science and Pollution Research, 2010)

Endosymbiotic copepods may feed on zooxanthellae from their coral host, Pocillopora damicornis - Y.-R. Cheng; C.-F. Dai (Coral Reefs, 2010)

Antimicrobial stewardship program directed at broad-spectrum intravenous antibiotics prescription in a tertiary hospital - V. C. C. Cheng; K. K. W. To; I. W. S. Li; B. S. F. Tang; J. F. W. Chan; S. Kwan; R. Mak; J. Tai; P. Ching; P. L. Ho; W. H. Seto (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Multiple alphaII-spectrin breakdown products distinguish calpain and caspase dominated necrotic and apoptotic cell death pathways - Zhiqun Zhang; Stephen F. Larner; Ming Cheng Liu; Wenrong Zheng; Ronald L. Hayes; Kevin K. W. Wang (Apoptosis, 2009)

The infection process of the reef coral Stylophora pistillata by the parasitic copepod, Xarifia obesa - Y.-R. Cheng; C.-F. Dai (Coral Reefs, 2009)

Planning of municipal solid waste management systems under dual uncertainties: a hybrid interval stochastic programming approach - G. H. Cheng; G. H. Huang; Y. P. Li; M. F. Cao; Y. R. Fan (Stochastic Environmental Research and Risk Assessment, 2009)

Application of Fractal Models to Distinguish between Different Mineral Phases - Renguang Zuo; Qiuming Cheng; Qinglin Xia; F. P. Agterberg (Mathematical Geosciences, 2009)

Lineage-specific diversification of killer cell Ig-like receptors in the owl monkey, a New World primate - Luis F. Cadavid; Cheng-Man Lun (Immunogenetics, 2009)

New Horizons for the Next Era of Human Brain Imaging, Cognitive, and Behavioral Research: Pacific Rim Interactivity - John Darrell Van Horn; Peter A. Bandettini; Kang Cheng; Gary F. Egan; V. Andrew Stenger; Stephen Strother; Arthur W. Toga (Brain Imaging and Behavior, 2008)

Genetic analysis of photoperiod sensitivity in a tropical by temperate maize recombinant inbred population using molecular markers - C. L. Wang; F. F. Cheng; Z. H. Sun; J. H. Tang; L. C. Wu; L. X. Ku; Y. H. Chen (Theoretical and Applied Genetics, 2008)

The clinical characteristics of Werner syndrome: molecular and biochemical diagnosis - Meltem Muftuoglu; Junko Oshima; Cayetano von Kobbe; Wen-Hsing Cheng; Dru F. Leistritz; Vilhelm A. Bohr (Human Genetics, 2008)

Antioxidative activities and the total phenolic contents of tonic Chinese Medicinal Herbs - D.-J. Guo; H.-L. Cheng; S.-W. Chan; P. H.-F. Yu (Inflammopharmacology, 2008)

Ly49h is necessary for genetic resistance to murine cytomegalovirus - Tammy P. Cheng; Anthony R. French; Beatrice F. M. Plougastel; Jeanette T. Pingel; Michael M. Orihuela; Mark L. Buller; Wayne M. Yokoyama (Immunogenetics, 2008)

Comparative leaf anatomy, FTIR discrimination and biogeographical analysis of Camellia section Tuberculata (Theaceae) with a discussion of its taxonomic treatments - H. F. Lu; B. Jiang; Z. G. Shen; J. B. Shen; Q. F. Peng; C. G. Cheng (Plant Systematics and Evolution, 2008)

Special Issue of Mathematical Geosciences to Honor Frits Agterberg - G. F. Bonham-Carter; Q. Cheng (Mathematical Geosciences, 2008)

GIS-based Mineral Resource Assessment - G. F. Bonham-Carter; Q. Cheng (Natural Resources Research, 2008)

Inhibitory effect of triptolide on interleukin-18 and its receptor in rheumatoid arthritis synovial fibroblasts - Y. Lu; W.-J. Wang; J.-H. Leng; L.-F. Cheng; L. Feng; H.-P. Yao (Inflammation Research, 2008)

Anatomically Realistic Three-Dimensional Meshes of the Pelvic Floor & Anal Canal for Finite Element Analysis - Kimberley F. Noakes; Ian P. Bissett; Andrew J. Pullan; Leo K. Cheng (Annals of Biomedical Engineering, 2008)

Screening of a high fibrinolytic enzyme producing strain and characterization of the fibrinolytic enzyme produced from Bacillus subtilis LD-8547 - Shi H. Wang; Cheng Zhang; Yan L. Yang; Miao Diao; Ming F. Bai (World Journal of Microbiology and Biotechnology, 2008)

Optimal Water Resource Allocation in Arid and Semi-Arid Areas - Jin F. Wang; Guo D. Cheng; Yi G. Gao; Ai H. Long; Zhong M. Xu; Xin Li; Hongyan Chen; Tom Barker (Water Resources Management, 2008)

Transcriptional analysis of a major capsid protein gene from Spodoptera exigua ascovirus 5a - T. Z. Salem; C. M. Turney; L. Wang; J. Xue; X.-F. Wan; X.-W. Cheng (Archives of Virology, 2008)

Leaf phenology and seasonal variation of photosynthesis of invasive Berberis thunbergii (Japanese barberry) and two co-occurring native understory shrubs in a northeastern United States deciduous forest - Cheng-Yuan Xu; Kevin L. Griffin; W. S. F. Schuster (Oecologia, 2007)

Seasonal variation of temperature response of respiration in invasive Berberis thunbergii (Japanese barberry) and two co-occurring native understory shrubs in a northeastern US deciduous forest - Cheng-Yuan Xu; W. S. F. Schuster; Kevin L. Griffin (Oecologia, 2007)

Investigation of rice transgene flow in compass sectors by using male sterile line as a pollen detector - Q. H. Yuan; L. Shi; F. Wang; B. Cao; Q. Qian; X. M. Lei; Y. L. Liao; W. G. Liu; L. Cheng; S. R. Jia (Theoretical and Applied Genetics, 2007)

The two giant sister species of the Southern Ocean, Dissostichus eleginoides and Dissostichus mawsoni, differ in karyotype and chromosomal pattern of ribosomal RNA genes - L. Ghigliotti; F. Mazzei; C. Ozouf-Costaz; C. Bonillo; R. Williams; C.-H. C. Cheng; E. Pisano (Polar Biology, 2007)

Developmental regulation of SSeCKS expression in rat brain - L. Chen; J. Qin; C. Cheng; H. Liu; J. Qian; L. Sun; F. Xiao; S. Shi; S. Niu; A. Shen (Journal of Molecular Neuroscience, 2007)

Src suppressed C kinase substrate regulates the lipopolysaccharide-induced TNF-α biosynthesis in rat astrocytes - L. -l. Sun; C. Cheng; H. -o. Liu; C. -c. Shen; F. Xiao; J. Qin; J. -l. Yang; A. -g. Shen (Journal of Molecular Neuroscience, 2007)

Antimicrobial potentials of endophytic fungi residing in Quercus variabilis and brefeldin A obtained from Cladosporium sp. - F. W. Wang; R. H. Jiao; A. B. Cheng; S. H. Tan; Y. C. Song (World Journal of Microbiology and Biotechnology, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Analysis of candidate genes on chromosome 2 in oral cleft case-parent trios from three populations - T. H. Beaty; J. B. Hetmanski; M. D. Fallin; J. W. Park; J. W. Sull; I. McIntosh; K. Y. Liang; C. A. VanderKolk; R. J. Redett; S. A. Boyadjiev; E. W. Jabs; S. S. Chong; et al. (Human Genetics, 2006)

Phthalate Ester Pollution in Urban Soil of Beijing, People's Republic of China - X. H. Li; L. L. Ma; X. F. Liu; S. Fu; H. X. Cheng; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2006)

QTL analysis for rice grain length and fine mapping of an identified QTL with stable and major effects - X. Y. Wan; J. M. Wan; L. Jiang; J. K. Wang; H. Q. Zhai; J. F. Weng; H. L. Wang; C. L. Lei; J. L. Wang; X. Zhang; Z. J. Cheng; X. P. Guo (Theoretical and Applied Genetics, 2006)

Single-Column Model Intercomparison for a Stably Stratified Atmospheric Boundary Layer - J. Cuxart; A. A. M. Holtslag; R. J. Beare; E. Bazile; A. Beljaars; A. Cheng; L. Conangla; M. Ek; F. Freedman; R. Hamdi; A. Kerstein; H. Kitagawa; et al. (Boundary-Layer Meteorology, 2006)

GGM02 – An improved Earth gravity field model from GRACE - B. Tapley; J. Ries; S. Bettadpur; D. Chambers; M. Cheng; F. Condi; B. Gunter; Z. Kang; P. Nagel; R. Pastor; T. Pekker; S. Poole; et al. (Journal of Geodesy, 2005)

Hypoxia-induced apoptosis in endothelial cells and embryonic stem cells - C. N. Lee; W. F. Cheng; M. C. Chang; Y. N. Su; C. A. Chen; F. J. Hsieh (Apoptosis, 2005)

Comparison of catches on two types of collector of recently settled stages of the spiny lobster ( Panulirus argus ) , Florida, United States - B. F. Phillips; Y. W. Cheng; C. Cox; J. Hunt; N. K. Jue; R. Melville‐Smith (New Zealand Journal of Marine and Freshwater Research, 2005)
This study compared catches of Panulirus argus pueruli and very young juveniles between Hunt and Sandwich collectors at Long and Big Munson Keys, Florida, United States. Catch comparisons were made over the peak puerulus settlement period between February and July 2002, using six Sandwich and six Hunt collectors at each site. The collectors were set out in arrays and the relative positions of the two collector types were reversed each month after they had been checked and the catch removed. A total of 3470 pueruli and juveniles were collected; 2011 and 1459 by Sandwich and Hunt collectors, respectively. Sandwich collectors caught an average of 5.43 more pueruli and juveniles per check than Hunt collectors, with this difference being significant for catches of clear pueruli (P1s), pigmented pueruli (P3s), and juvenile stages (J1s and J2s) ( P 0.05), but not for catches of semi‐pigmented pueruli (P2s). The catches made by both collector types were highly dependant on the month of collection and site of the collectors ( P 0.01). Catches were generally not influenced by the location of the collector in the array ( P = 0.50), but corner collectors caught significantly fewer P1s, P2s, P3s, and J1s and J2s than all other collectors ( P 0.01). Conditioning time influenced the total catch ( P 0.01) but was not significant for all individual P1s, P2s, P3s, and J1s and J2s stages of development. Overall, the time taken for collectors to condition in Florida was less than the Sandwich collectors used for P. cygnus in Western Australia.

The relationship between HPV16 and expression of CD44v6, nm23H1 in esophageal squamous cell carcinoma - W.-K. Liu; Y.-L. Chu; F. Zhang; P. Chen; F. Cheng; H. Wang; Y.-Y. Jia; T.-Y. Ma (Archives of Virology, 2005)

Nitrogen Leaching and Denitrification in Continuous Corn as Related to Residue Management and Nitrogen Fertilization - Hero T. Gollany; Jean-Alex E. Molina; C. Edward Clapp; Raymond R. Allmaras; Milegua F. Layese; John M. Baker; H. H. Cheng (Environmental Management, 2004)

Lymphocyte surge as a marker for immunorestitution disease due to Pneumocystis jiroveci pneumonia in HIV-negative immunosuppressed hosts - V. C. C. Cheng; I. F. N. Hung; A. K. L. Wu; B. S. F. Tang; C. M. Chu; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Effect of organophosphorus hydrolysing enzymes on obidoxime-induced reactivation of organophosphate-inhibited human acetylcholinesterase - S. Herkenhoff; L. Szinicz; V. K. Rastogi; T.-C. Cheng; J. J. DeFrank; F. Worek (Archives of Toxicology, 2004)

Comparison of inhibitory effects of oxygen radicals and calf serum protein on surfactant activity - M.M. Lee; F.H.Y. Green; S. Schürch; S. Cheng; S.G. Bjarnason; S. Leonard; W. Wallace; F. Possmayer; V. Vallyathan (Molecular and Cellular Biochemistry, 2004)

Mating Behavior of Cephalonomia tarsalis (Ashmead) (Hymenoptera: Bethylidae) and the Effect of Female Mating Frequency on Offspring Production - Ling-lan Cheng; Ralph W. Howard; James F. Campbell; Ralph E. Charlton; James R. Nechols; Sonny B. Ramaswamy (Journal of Insect Behavior, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Alteration of Soil Carbon Pools and Communities of Mycorrhizal Fungi in Chaparral Exposed to Elevated Carbon Dioxide - Kathleen K. Treseder; Louise M. Egerton-Warburton; Michael F. Allen; Yufu Cheng; Walter C. Oechel (Ecosystems, 2003)

Genomic characterization of Rim2 / Hipa elements reveals a CACTA-like transposon superfamily with unique features in the rice genome - G.-D. Wang; P.-F. Tian; Z.-K. Cheng; G. Wu; J.-M. Jiang; D.-B. Li; Q. Li; Z.-H. He (Molecular Genetics and Genomics, 2003)

Risk Factors for Development of Paradoxical Response During Antituberculosis Therapy in HIV-Negative Patients - V. C. C. Cheng; W. C. Yam; P. C. Y. Woo; S. K. P. Lau; I. F. N. Hung; S. P. Y. Wong; W. C. Cheung; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Behavioral Interaction Between Males of Cephalonomia tarsalis (Ashmead) (Hymenoptera: Bethylidae) Competing for Females - Ling-lan Cheng; Ralph W. Howard; James F. Campbell; Ralph E. Charlton; James R. Nechols; Sonny Ramaswamy (Journal of Insect Behavior, 2003)

Agrobacterium-mediated large-scale transformation of wheat (Triticum aestivum L.) using glyphosate selection - H. P. Zhou; N. Biest; G. Chen; M. Cheng; X. Feng; M. Radionenko; F. Lu; J. Fry; T. Hu; S. Metz; C. Chay (Plant Cell Reports, 2003)

A novel method to induce direct somatic embryogenesis, secondary embryogenesis and regeneration of fertile green cereal plants - F. Eudes; S. Acharya; A. Laroche; L.B. Selinger; K.-J. Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Null mutations in the N-acetylglutamate synthase gene associated with acute neonatal disease and hyperammonemia - Ljubica Caldovic; Hiroki Morizono; Maria Gracia Panglao; Sabrina F. Cheng; Seymour Packman; Mendel Tuchman (Human Genetics, 2003)

Characterization and Temporal Variation of Asian Dust Aerosol from a Site in the Northern Chinese Deserts - X. Y. Zhang; S. L. Gong; R. Arimoto; Z. X. Shen; F. M. Mei; D. Wang; Y. Cheng (Journal of Atmospheric Chemistry, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

Illumination and turbidity effects on observing faceted bottom elements with uniform Lambertian albedos - Kendall L. Carder; Cheng-Chien Liu; Zhongping Lee; David C. English; James Patten; F. Robert Chen; James E. Ivey; Davis Curtiss O. (Limnology and Oceanography, 2003)
Aircraft images were collected near Lee Stocking Island (LSI), Bahamas, with wavelike features for bright sand bottoms during times when solar zenith angles were large. The image contrast between leading and trailing wave facets approached a 10–15% difference because of algae accumulations in wave troughs or topographic variations of the bottom. Reflectance contrast for blue light was greater than for red and green wavelengths when algae or detritus was present in the troughs. However, the contrast at green and red wavelengths was greater than at blue wavelengths when caused by the interplay between bottom topography and oblique illumination. A three‐dimensional backwards Monte Carlo (BMC) model was developed to evaluate the effect of oblique illumination on wavelike topographic features for various values of water clarity and bottom albedo. An inverse optical modeling approach, previously developed for flat, horizontally homogeneous bottoms, was applied to the BMC results. Bathymetric estimates for bright facets tilted 10° toward the sun were slightly smaller than actual depths, whereas shaded facet depth estimates were too high by about 5%. Larger errors were associated with albedo retrievals, where shaded facets produced albedo estimates up to 15% lower than actual values. Errors increased with tilt angles up to 20° but decreased with sea and sky turbidity. Averaging sunlit and shaded pixels before running the inverse model reduced the uncertainty of bathymetric and albedo estimates to about 2 and 5%, respectively, comparable to previous field evaluations of the inversion model.

RFLP-facilitated investigation of the quantitative resistance of rice to brown planthopper (Nilaparvata lugens) - X. F. Xu; H. W. Mei; L. J. Luo; X. N. Cheng; Z. K. Li (Theoretical and Applied Genetics, 2002)

Seasonal dynamics of coastal ecosystems and export production at high latitudes: A modeling study - Ru Cheng Tian; Alain F. Vézina; Michel Starr; François Saucier (Limnology and Oceanography, 2001)
Export of organic matter from the surface to deeper waters often shows much smaller seasonal variations than primary production or nitrate‐based new production in mid‐ to high‐latitude marine systems. The mechanisms underlying this pattern remain poorly understood, but seasonal shifts in food web structure and dynamics have been implicated. We report here on an ecosystem modeling analysis of a high‐resolution (biweekly) time series of biomass, production, and export flux (sediment trap) measurements conducted in 1991 in Bonne Bay (Newfoundland). This time series shows the classical pattern of a spring bloom followed by a summer low biomass period, yet export is bimodal, with maxima during spring and late summer. The ecosystem model was forced by diagnostic vertical mixing calculations based on temperature and salinity records taken every 3 d and hourly wind data. The physical analysis indicated that the nitrate flux into the euphotic zone during summer was equivalent to that during the spring and fall seasons and accounted for half of the summer export. Statistical adjustments of the parameters of the ecosystem model indicated that strong production of dissolved organic carbon during the spring bloom, high temperature dependence of microbial activity, and physico‐chemical particle aggregation played key roles in explaining the remainder of the summer export. Seasonal changes in trophic pathways between spring and summer, such as a shift from a herbivorous to a microbial food web, played a comparatively smaller role. Our modeling analysis suggests that physical mixing processes and physico‐chemical aggregation processes are at least as important as shifts in food web trophic pathways in explaining the postbloom export flux in mid‐ to high‐latitude marine systems.

Establishment of a gene transfer system for Pseudozyma flocculosa, an antagonistic fungus of powdery mildew fungi - Y. Cheng; F. Belzile; P. Tanguay; L. Bernier; R. Bélanger (Molecular Genetics and Genomics, 2001)

Special Issue of Transport in Porous Media on ‘Seawater Intrusion in Coastal Aquifers’ - Alexander H.-D. Cheng; Leonard F. Konikow; Driss Ouazar (Transport in Porous Media, 2001)

Cryopreservation of heart cells from the eastern oyster - Ta Chih Cheng; Jerome F. La Peyre; John T. Buchanan; Terrence R. Tiersch; Richard K. Cooper (In Vitro Cellular & Developmental Biology - Animal, 2001)

CRYOPRESERVATION OF HEART CELLS FROM THE EASTERN OYSTER - TA CHIH CHENG; JEROME F. LA PEYRE; JOHN T. BUCHANAN; TERRENCE R. TIERSCH; RICHARD K. COOPER (In Vitro Cellular & Developmental Biology - Animal, 2001)

Mitochondrial DNA sequence variation and phylogeography of oceanic insects (Hemiptera: Gerridae: Halobates spp.) - N. M. Andersen; L. Cheng; J. Damgaard; F. A. H. Sperling (Marine Biology, 2000)

Physical mapping of the human ATX1 homologue (HAH1) to the critical region of the 5q- syndrome within 5q32, and immediately adjacent to the SPARC gene - J. Boultwood; A.J. Strickson; E.W. Jabs; J.-F. Cheng; C. Fidler; J.S. Wainscoat (Human Genetics, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Polyploidization in embryogenic microspore cultures ofBrassica napus L. cv. Topas enables the generation of doubled haploid clones by somatic embryogenesis - X. XuHan; H. -C. Jing; X. -F. Cheng; A. Iwanowska; H. Kieft; J. H. W. Bergervoet; S. P. C. Groot; R. J. Bino; A. A. M. van Lammeren (Protoplasma, 1999)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Fuzzy Weights of Evidence Method and Its Application in Mineral Potential Mapping - Qiuming Cheng; F. P. Agterberg (Natural Resources Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Expression of neurotrophins, GDNF, and their receptors in rat thyroid tissue - N. Belluardo; G. Mudò; G. Caniglia; M. Corsaro; Q. Cheng; F. Frasca; A. Belfiore; D. F. Condorelli (Cell and Tissue Research, 1999)

Identification and purification of a spinach chloroplast DNA-binding protein that interacts specifically with the plastid psaA - psaB - rps14 promoter region - M. C. Cheng; S. P. Wu; L. F. O. Chen; S. C. G. Chen (Planta, 1997)

Gastric Cancer Mortality and Drinking Water Qualities in Taiwan - C.-Y. Yang; H.-F. Chiu; J.-F. Chiu; M.-F. Cheng; W.-Y. Kao (Archives of Environmental Contamination and Toxicology, 1997)

Comparison of E-test with agar dilution for determining susceptibility ofStreptococcus pneumoniae to penicillin - O. Scheel; D. J. Lyon; D. N. C. Tsang; A. F. B. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Aluminum Toxicity and Nutrient Utilization in the Mycorrhizal Fungus Hebeloma mesophacus - F.-X. Kong; Y. Liu; F.-D. Cheng (Bulletin of Environmental Contamination and Toxicology, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

Production and cytogenetics of Brassica campestris-alboglabra chromosome addition lines - B. Y. Chen; B. F. Cheng; R. B. Jørgensen; W. K. Heneen (Theoretical and Applied Genetics, 1997)

Cloning and expression of an amylase gene from Streptococcus bovis in Escherichia coli - Rhonda G. Clark; Y. -J. Hu; Michael F. Hynes; R. Keith Salmon; K. -J. Cheng (Archives of Microbiology, 1992)

Method for quantitating cholesterol in subfractions of serum lipoproteins separated by gradient gel electrophoresis - M. -L. Cheng; C. M. Kammerer; W. F. Lowe; B. Dyke; J. L. VandeBerg (Biochemical Genetics, 1988)

Method for quantitating cholesterol in subfractions of serum lipoproteins separated by gradient gel electrophoresis - M. -L. Cheng; C. M. Kammerer; W. F. Lowe; B. Dyke; J. L. VandeBerg (Biochemical Genetics, 1988)

Lipid composition of potatoes as affected by storage and potassium fertilization - F. C. Cheng; P. Muneta (American Journal of Potato Research, 1978)